UPAYA PENINGKATAN PEMBELAJARAN MATA KULIAH FREJER VORTRAG II - Triyono, Sulis; Sahayu, Wening (LITERA, 2015)
<img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAiMAAAKxCAIAAAAO5juuAAAgAElEQVR4nOydZ1BbWZr336r9NjVVszUzPds93T0dt3vabud2Y+Ns44iNMRiDyWDAZLAJBoMBm5wRyWARRc4IgZBAgAJJAglJSIAACQmRBCgTFBB6P5xaFa/d09sz237Xnrm/D67y5d5zz72Szv+E5zz//6OHgICA2MPu7u7/dhUg/tn4P//bFYCAgICA+CcHUhoICAgIiLcLpDQQEBAQEG8XSGkgICAgIN4ukNJAQEBAQLxdIKWBgICAgHi7QEoDAQEBAfF2gZQGAgICAuLtAikNBAQEBMTbBVIaCAgICIi3C6Q0EBAQEBBvF0hpICAgICDeLpDSQEBAQEC8XSClgYCAgIB4u0BKAwEBAQHxdoGUBgICAgLi7QIpDQQEBATE2wVSmneC3d3dnzQ6/OXuhz9ZAmSe+JP8rXf1S17X3zrnF77q3f/il5z8v8jeGv5dj/wz3+T/9qn/1sv5u17au/9u/zWBlOadYHd3V6vVyuXypaUlHo83Ozu7sLCwubmp0WjEYjGXy+VyuQsLC0KhcG5ujsvlMpnM/v7+/v7+qakpiUSys7MDClGr1UqlUiaTKZVKlUoFClepVDwej06nT09PG07W6/UKhYLL5c7PzxvOFIvFc3NzYrH4zRpqNJrV1VUOh0OlUgcGBohE4sDAAIPBWF5elslkfD5/ZGRkaGiITCZTKJSxsTEOh8Pj8WZmZlgsFpvNFolEhqKWl5fZbDaHw1lYWJifn5+YmKBSqUwmUyAQCIXCqampiYmJxcXF7e1tcP7GxgaPxxsfH+dyuRsbG+CgSCQaGxsbGBjA4/FdXV19fX10On1lZWVra0sikUxOTg4PD9PpdIlEotfr19fXmUwmg8EQCoUbGxugMVIqlTweb25uzlDm7u6uUqmcnZ0lk8ngcgaDQaFQSCTSyMiIUChUqVTgk9rY2FhbW1tZWZHJZIaXv7m5ubS0xGazp6am5HI5KFOpVE5PT9NotImJCZFIpFarQaO5srIyOjra09PT1dWFwWDweDydThcIBEtLSxwOZ2BgoK+vj0wmk8lkIpHIZDKXl5dnZ2f7+/tJJNL09LRCoTC8z+3tbYFAAD6UyclJHo9Ho9GIRCIej8fhcD09PRQKhcvlisVikUg0Pj6Ox+P7+voGBweHhobodDqXy52dnR0bGyORSIODg5OTk2Kx2PAlMXyvBAIBi8Wam5tTKBSGR5bL5ZOTk+BeTCZTLBYbJGFzc5PNZo+MjCwtLYFydDqdQqGYmZkhkUhdXV29vb2gemNjYysrK4Y3s7OzI5fLBQIBm82enZ1VKpWGOiwvL4+Ojvb29o6Pjxu+HisrKywWi8lk8vl8pVIJKc27CaQ07wpqtXphYaG3t7ekpKSkpIRAIKytrW1tbTEYjPr6+ra2tqGhISKR2NLSUlJSkpqaGhERERERkZ2d3dvbu7q6CgoRiURUKrW3t5dMJi8sLICDMpkMi8XCYLD8/Hw8Hr++vg6OT0xMIJFIAoEAmi2VSoXD4YqLi/v7+/c2NICNjQ0Wi1VZWfns2bPHjx+DuycmJnZ2djIYjKampmfPnoWFhSUlJWVlZRUXF7e0tKDR6MbGxpycnOTk5NbWVtDo6/X6gYEBOBxeV1c3NDTU19dXVFQUFRWVlpaGwWD6+/srKythMFhtbS2LxQISuLq6ikajCwsL29raFhcX9Xq9WCzG4XAwGCw+Pj4qKurRo0dPnjzJzc2lUChra2vj4+OFhYVPnz7Nzs4eGxuTSqUUCuXVq1clJSWDg4OGdzUzM1NaWlpUVESn07VarV6v393dXV5e7uzszMjISExMzMrKyszMjI2NjYyMzM7OHhgYAC9qY2NjZmYGh8O1t7dTqdStrS1Q4Pr6+sDAQF5eHgwGGxgYAAcXFxcbGhoyMjIqKyvpdLpB1SgUSnJy8oMHDxwdHV1dXYODg1NTU2tra3t7eysrK319fZ2dnRMTE7Ozs1+8eFFRUUGlUpuamvz8/FxcXLKzsxkMBihnZ2eHx+MhEAg3NzcvL6+qqioMBpOZmRkYGOjv7//w4UN3d/eIiIjKykoGg0GlUnNyclxdXb29vePj49PS0kpLS7FYLAqFysjI8PPz8/f3f/Xq1cTEBHghBiQSSWNjY3x8fHFxMZ1OB62/Xq/n8/kVFRU+Pj4uLi5ZWVmTk5OGSyYnJ1NSUkJDQ7FYLDii0+mWlpbq6+s9PT3v3bvn7+/v5+fn4eGRmJiIx+PX1tbAaSqVanJysra2NiEhAQ6HczgccFypVFKp1JSUFBcXl9jYWCaTCX41FAqluLi4sLCwu7sbfD0g3kEgpXlX0Gg0IpEIgUDY2dl5enpisVipVLq9vd3T05OZmVlbW0ulUvF4PAwG8/DwcHV1jYyMDA0NtbGxefz4cV9fH9AGGo2WkpLi4eHx/PlzEokESlYqlb29veHh4RYWFmFhYVQqFYxm2traKioq+vv7wQCIxWKFhobeunUrIyPD8LM3sLW1NT09nZKScuXKlbt37yYkJAQFBd25c+fZs2f19fUvXrwwNzd3cHBISUmpqanp6OjAYDBtbW2lpaW+vr7nz5+3sbGpra1dWFjQarU4HC4+Pr6srAw8UVxcnJmZmYuLS1NT09DQUHZ2trW1tZWVVWpqKovF0uv1crkciUQmJyc3NTUJBIKZmZnm5ua0tLS4uDgYDPby5cu0tLT4+PjU1NTe3t7l5WUCgRAUFOTg4BAfH49GowcGBhoaGnJzc2traxkMhkHwCASCi4uLmZlZbm4uj8cDL1AkEhEIBDgcnpCQEBkZCdrrZ8+elZWVjY6OghZ2dXUVi8VGR0cHBAQgEAipVAoKlEqlPT09/v7+ZmZmERERdDp9e3tbJBJVVFRER0eXlZUxmczNzU1wcn9/f1hY2JUrVy5fvvzgwYMnT564u7v7+fmVlpZmZGQYGxsfPXo0MTERiUQWFRW1t7ez2eyysrKLFy9+9NFHV69erays1Gg0er1+c3OztbXV2tr6o48+Onv2bGlpaXd39/Pnz+3s7Jydne3t7c3NzS0tLcPDw0H/Iygo6PDhw5aWljk5OVVVVe3t7QMDA0gkMiIi4tKlS8bGxmFhYQwG47WuxtzcXFhY2I8//mhhYVFRUWHoxHC53Nzc3CtXrhw+fDggIAB8XuA11tTUXL9+/eTJk9nZ2WCEt7u7u7a2VlhYePTo0f379/v4+AQFBVlaWjo5ORUUFLDZbHDt5uZmV1eXj4+PkZGRra0tDoczfAOZTGZkZOQPP/xgZGQUFxfHZrOVSiWZTM7OzobBYFgsFlKadxZIad4Vdnd3NRoNHA4/evTorVu3hoeHtVrtzs4OGo3OysrCYrGrq6uTk5Pp6enXrl2zsrIqKSnJzc01NjY+efJkSUkJmHzo6uqytbX9y1/+cvr0aTgcDsYEOzs78/PzeXl5xsbGFy5cKCkpIZPJdXV1r169wmAwQqFQo9GsrKzU1NRcvnz5yy+/fPjw4ejoqGFKDaDT6ZRKZXZ29vHjx+3s7EAv+MyZM/b29vn5+SEhIaampu7u7qD3zeVyJycnyWQyEokMCgo6dOjQ559/fu/evaamJqFQ2NvbC4PB0Gi0SCSamppKT0+/evWqnZ0dFovl8/llZWXXr1/ft2/fjRs38vPzeTyeQqEgkUhFRUVEIpHP5yMQCFdXV39//5qaGhaLtby8vLS0xGAwMBjM2NiYWCzu7e0NCAjw8PBIS0t7+fJlTk5OeXl5b28vmHwDvfWtra2Wlpbbt29/99139+7dq6+vB0O9zc3N1dXVqakpNBqdkZEREhISFxfX1tbG4/HEYjFo3IVCYUVFhZWV1enTp589e2ZodlUqFYVCCQkJMTY2PnfuXFJSEpvNXl5ebm9vLy4uxuPxKysrhrECk8nMyclxcXF58OBBdnY2AoHw9va2s7MrLS199eqVkZHRkSNHysvLFxYWwJyVVCpFoVC3b9/+zW9+8/nnn0dGRgqFwt3d3YWFhYyMjEOHDv3bv/2biYkJFoudnZ0tLi4OCgqKiIgIDw/39PS0srLy9/fv6+ubmpqKiIg4duyYh4dHZ2cnlUqdmppaWloaGxvLzs42NTU9fvx4aGjo9PT0a+s0NBrN19f3q6+++s///M/Hjx/TaDTwp8XFxerq6rt37x49ejQoKEggEIDjo6Oj0dHRx48fP3r06NOnTxkMBpjs0mg0VVVVBw4cOHbsGAwGQyAQgYGBHh4e2dnZo6Oj4KYKhaKhocHc3PyPf/zjjz/+WFxcDIRKp9OJRKKysrJbt259/vnn586dy87OZrFYIyMj9fX1SCSSyWQaVB/iXQNSmneLwsLCL7/88vLly+Pj4+BIR0dHdnY2iURSqVSgWTl9+vS5c+fi4+MjIyO/+eabo0ePVlRU7OzsqFSq7u5uV1fX3//+9x988EFQUBCfzwedU41G09vba21t/cMPP7i7u8fFxUVERLx8+ZLFYqnVar1ePzExkZycbGJicuzYMQcHh7q6up/sHpaUlBw8ePDq1avFxcXh4eEHDhxwcHBAIBDR0dGXL1++c+dOREREfn5+W1vb6Ogok8nE4XDZ2dnOzs4HDhz4+uuvPT09W1tbm5qaCgoK+vv7FQoFn8/Pzc29du2anZ0dmEKpr693cnK6cuXKiRMnrl27lpWVNT4+PjAwUFFRMTw8PDY2FhgYePDgwYcPH1IolL1db4VCIZfL1Wo1kUgMCgqysbFxd3d3cXF59OhRU1OTYc5Qr9dvbGxMTU3V19eHh4dfvHjx4MGD/v7+YD4KNHY7OzsMBqOgoCAoKCglJWV0dHTvS1hYWKiurrawsDhw4ICXl9f4+Di4Ckx1FhQU2NjYHDx48MaNG4WFhYODg2g0GoVCTUxMGJaI9Hr99PQ0AoF49OiRl5dXQkJCXl7ekydPnj59ikajKysrT5069dVXX0VERHR2dqLRaDabvbGxMTg46OHh8Ze//OXLL790cXFBoVAsFotMJsNgsAsXLvzud7+7fv36wMAAmOkKDg728vJydHS0srKytLR8+vQpjUZbXFxMSko6ceLEvXv3UlNTYTBYU1PTwsLC4uJiVVWVhYXFjz/+GBYWxufzDQ+r0WiEQmFPT09eXp6Dg8PXX3996dIlJBIJ/ioSiVpbWx0cHIyMjJ48ebK8vKzX63U6XVdXV0hIyK1bt8zMzLy9vSsrK4VCIbikpaXl8OHD33//fWxsbG5uLhgyYrHYubk5cALQVBcXl6+//vrQoUPh4eE0Gg2MBeVyeW9vb1RU1IULF44cOWJpaZmamlpXV9fZ2Ukmk/cuuUG8a0BK827x6tWrb7755saNG1NTU+BIZ2dnbm4ukUjc2toSCoVZWVlnzpw5cOCAvb39w4cPr1y54uPjMzw8rNFo+Hw+BoOJiYk5cODA7373OwsLi66uLsPS8fz8fEFBgaWlpbGx8ZUrV/z8/Jqbmw3tb29vb2hoqLW1tY2Nja2tbUxMDIVCebN65eXl+/fvP3ToUFhYmI+Pz40bN1JSUvr7+3Nyci5fvnzmzJnbt29bW1uDtgMoTWtra319fUhIyKlTpy5evBgYGPjs2bPk5OTe3l6RSDQ9PZ2bm2tqaurg4NDX17e8vNzc3JySkpKTk+Pu7r5v376rV6/m5uaWlJRkZ2f39fXh8fj79+9/+umn3t7e09PThoptb2/L5fLNzc2dnR0ymRwWFmZiYmJkZHT06FEbG5v6+nrDtJVer19ZWWlraysuLq6srPTz8/viiy/Onz/f3NxsOEen09Hp9Pz8/ICAgPj4+L2vQqlUTkxM1NXVPXjw4OTJk05OTp2dnQqFQqfTSaVSBoOBxWKzsrJsbGwuXbrk7Oz84sWLzMzMuro6JpMpl8v3Kk15ebm/v7+9vb2Hh8eLFy8KCgowGMzk5GRlZaWxsfGf/vQnS0vLmJiYpKQkHA4nkUhGR0fDw8Nv3rx5+/Zte3v7kJCQrKysmpqahoaGkJCQ77///vr163g8HiiNh4fHrVu3TExMrl+/bmlpGRkZCZQmLS3txx9/PHfu3P3798Hk58TEhFgsrquru3PnzokTJ54+fTo/P7/3xRKJRAQCgUaji4qKjI2N9+3bl5OTAzooq6urra2tdnZ2RkZG4eHhYPF/fX29sbExLCzM29vbzc3t7t27oaGhIyMjoEAkEnns2LHPP//c1dXVw8PDzMwsISFhfn4edBq2tra4XC4SiQwLC7t8+fLx48ctLS1LS0tByVKpdHR0tL6+Pj4+3s3N7fLlyyYmJp6ensXFxUQikcvl7v2UId4pIKV5tygsLPz2229v377N4/HAka6urvz8fCKRuLGxIRAIMjMzz549e+TIER8fn8LCwrKyMhwOt76+vrKy0tnZmZ+fHxoaevTo0d/+9rdGRkY5OTmGrqJarR4bGwsLC/v222+/++67iIgIBoMBJnNkMllZWZm1tbWpqamFhYWxsfGdO3fa2tpeq9vu7i4cDv/uu+9+/PHH/Pz82tra8vJyCoUiEAiKioosLCwsLS2BkJSUlNBotKmpKRwO193dTaPRenp6EhMT79y5c/LkyVOnTnl6eiKRSIFAMDU1lZeXZ2Zm5uTk1NfXt7KyAuIIxsbG6uvrLSwsjhw5cuPGDWtr66CgoO7ubjwef/fu3T/84Q8PHjyYnZ3V6/UajYbFYjU0NJSXl5NIJIlEQqVSw8PDr1+/bmxs/MUXXxw+fDgiIoLJZILGUa/XC4XCnJyc8PDw7OxsT0/Pjz/+eN++fenp6Xw+HyiBTqej0WhgVjAtLc0wptne3mYymU1NTRkZGc7OzmfPnjU3N4fBYBwOR6vVKhQKJpNJIBBQKFRRUVFQUNDly5ePHTt28+bNhIQEIpG4N6hvenq6rKzM29vbwcEhMjISiUTSaDSRSLS+vl5WVvbDDz989dVXT548aW1tbWtrY7FYm5ubZDI5NjYW6LSzs/PJkyevX78eFxeHxWJfvXp18eJFU1PTvr4+sVjc0NDg7e3t5OT0+PHj6OhoR0dHa2vrpqammZmZ2NjYw4cP3759Oy4uLi4urqqqanV1VSaTAaU5efJkdHT0ysqKoZ7b29uNjY0RERE5OTnp6elnz5799ttvw8LCZmZm1Gq1RCJBIpG2trZGRkaRkZGLi4sqlYpKpcJgMG9vb2dn59u3b3///fdmZmZdXV2gwLa2th9++OG7777z8/NzcnI6duxYQECAYRS1sLDQ3t6elpbm6el57dq1gwcPHjhwIDg4GPQqwFJNX19fX19fY2Ojp6fnX//61/3793t4eFRVVYEq/Xq/RYhfE0hp3i3gcPhf//rXy5cvk8lklUqlUqlaW1vT09N7enqUSqVAIEhLSzt16tSZM2fy8/NBJDRYoaHRaOnp6U+ePHny5ImlpeX+/fv379/v7u6Ow+F0Oh0oXCwWw2Cw//zP//z6668Ny/5KpXJkZCQlJcXJycnBwcHW1vabb77Zt29fZmYm6Kob6qbVajMzM8Hk3vDw8NbW1tbWlkajkUgkhYWFtra23t7epaWleDyezWbz+XwajdbW1tba2kqhUBYWFiYmJtLT00+dOvWnP/3p3Llz+fn5IKA5MzPTxMTEysoKi8UKhUIkEglW/peWlqqqquzt7Q8dOvTFF1+Ym5sjkUg6nR4aGvrXv/7V0tISjUaLxeL5+fnq6ur79++fP3/+xYsXHA6HTCYHBgbeunXLysrq7NmzBw8evHbtWmJiIplMVigUm5ubTCYzNjbWw8MjOjra29v72LFjYB4Mg8GAIaBWqyWRSPHx8R4eHnFxcWBMs7u7C6K8YmJiYmJiQkJCHB0dTU1NnZ2d6+rqVldXxWLxwMBAfX19e3s7g8Ho7u728PD4+OOPP/zwQxsbm9dm8Nhsdm5u7v37921tbcvKyqRSqVar3d3dlclkL1++BA0o6MuDAHeJRIJCocLCwvLz8zs6OgICAr744osDBw6Eh4d3dna+evXq3LlzJiYmnZ2d8/PzZWVlPj4+jx8/LiwsrKysdHFxOXnyZG5uLovFevLkyddff21vb49CoYaHh1ks1tra2tTUVGFhoampKVjYp9PpUql0aWlJLpcvLi4WFxc/ePAgMDAwPDzc3Nz8xIkT1tbWIC5AIpG0t7eDMc2zZ89A1HhpaWl4ePijR4+8vb1v3Ljx4YcfHjx48OXLlyDwpLa29vvvvz9w4EBMTExoaOiJEyfMzMyqq6uXlpZWV1e7urqeP3/u6+vr5eVlb29vZGT04YcfXr9+vb29XaFQiMViEonU1NQ0MjIyPz8P+iKffPLJ8ePH4+PjORzOmzGTEO8IkNK8WyAQiIMHDx48eDA7O5tKpY6Pj+fl5YWFhaFQKIVCIRAIkpKSfvjhh3PnzjU0NOy9EIPBBAUFRUZGNjU1NTQ0PHr06MCBA0eOHElLSzN0pbe3t1++fPnZZ5/9+c9/Tk1Nlclku7u7DAYjLy8vLi6urKyspaWltLT0/PnzH3zwgZOT09DQkEwmM9xCpVIlJiZ+9NFHFy5coNPphuMKhSIvL+/OnTt2dnZ5eXkEAoHBYPT399fV1cHh8LKyMhCHrVarqVRqcHDwl19++dlnnwUFBY2MjFCpVDDdd/bs2bq6OhaLBYfDc3NzQbzswsJCeXm5paXlxx9/fPz48aKiIoFAgEKhHB0dr169+ujRo8bGxq6uruTkZGNj448++sjDw4NGo+HxeCcnp9OnT9vZ2YHlinPnzhkZGQUHB6PR6P7+/oaGhsjIyKioqPr6+qqqKm9vbzChFB8fz+VywZMikUgXFxdjY+MHDx709PTo9Xq1Wt3V1RUYGOjj41NeXo7D4aqrq62trffv3+/t7T08PMxms+vq6tLS0qqqqng83vr6eltbm5mZ2R/+8IcTJ06Ul5cbNtno9XoymRwREQFmMktLSw2Kvr6+npGR8cknn3z44YfR0dG9vb1tbW04HI5CocBgMCcnp5ycnMHBwRcvXhw5csTExCQtLQ2FQsXHx+/bt+/YsWMVFRWjo6Opqan37t2ztbV9/PhxWFiYubn59evXq6urp6amQkJCPvzww7Nnz2ZmZjY0NKBQKDQaXVVVFR0dff78+U8//fTq1avZ2dlVVVWFhYUtLS0YDCYlJcXHxwcGgzU2NiYnJ5uamh48eNDV1ZVAICwvL3d0dIB1msjISDqdjkaj/fz8Hj9+jEAgUChUbGzsgQMHPvjgA3t7+66uLg6Hk5ubC76BgYGBSUlJjo6OFy9etLa2zsvLa2lpiYmJsbGxCQ8Pr6qqAqEfH3300ccff+zv74/BYEZGRioqKmJjY5FI5MbGBtDUixcv7t+/Pzg4eGJiAlKadxZIad4turu7HRwcLly44OvrC4fDKysrwZYRHA4H1s8zMzOvXr169+5dFAplmPRXKBRNTU1PnjyBw+HLy8tbW1ttbW3m5uZHjx4NCwubnp7e2dnZ3d2VSqWvXr06efLkkSNHUlNTl5aW1Go1DoeLiIjIysricrlqtXppaSk6OvrkyZPW1tZ1dXWGwCqwqzE3N/fkyZOWlpYkEmnv3auqqtzc3JydnZOSkpqamrq6uhobG+FweGFhYUVFRVdX19zcnEajUalURCLx4cOHZ8+ejYyMpFKpNBotKSnpwoUL5ubmjY2NNBoNRC0blkbm5ubKyspsbGzMzc1LS0ulUunq6mp1dTWYnImPjwe7ixwcHExNTRMTE9lsNpFI9PPzu3HjRmBgYEtLS1dX16NHj4yMjKytrXNycqqrq+FweFZWVktLy8LCwtLSUmNjo7u7+507d54/fw6W91UqVXt7u4eHx7lz5zw9Pfv6+vR6/fb2NgqFCg0NBXfRarVLS0sJCQnnz59/+PBhV1cXhUKpra3Nycmpra2dmZnR6/Wbm5u1tbVWVla2trZtbW17w/moVGpSUpKFhYW9vX1lZaVB0dfW1ioqKm7cuGFkZOTv75+dnQ324nR3d+fl5QUGBhYXF1Op1MrKykePHiUnJ2OxWAKBkJGRcePGjbt371ZXV4M9Pb6+vu7u7m5ubu7u7p6enklJSUwmc2lpKT8//8qVK7du3QoLCwPrYQUFBS9fvkxNTXVzc7t06ZKVldXz588TEhKePXuWm5tbX19fWFgIh8PBQGdkZCQqKurKlStubm5YLJbL5TY2Njo7O5uYmMTFxdFotObm5pCQkNzcXC6Xq9VqaTRacHDwuXPn7O3tgQqWlpZeu3bt9OnTkZGR9fX1paWl/v7+d+7cAd/eiIgIf3//hoaG1dVVkUhUVVV19+5dIyMjV1dX0GVBIBCxsbF1dXVg9LmyspKVleXq6gqDwbhcLqQ07yyQ0rxbCASClpaWpKSkyMjImJgYsH+woaFhdnZ2Y2NjdnYWgUA8efIkLi4Oj8eDWCaw5bO5uTkrKwuDwYDmDEyIPXr0CAaD0Wg0EN27vLzc2NgYEhISEBBQVlbG5/O3trYGBwezsrIQCAQINtNoNH19fcnJyYmJia2trYbFYY1Gs7a2hkaj4+PjMzIyBgcHpVIp+GGrVCrQ2Xz16lV9fX1XVxeRSOzr6+vq6urq6sLhcENDQwKBAIQIy2QyDAYDVr+FQuHs7CwSiUxLSysoKKBQKBwOp7Ozs6WlZXx83BCizePxmpqaioqK+vv7wUGBQIDFYsG+y7KysrKyMrC8PzQ0tLKywmazKysr09PTQS9+dXW1p6cnPT09JyenubkZg8Gg0eiurq6JiQm1Wq3T6WZnZ1EoVEVFBRqN5vP5Wq1Wo9GMj49XV1fDYLD6+nogG1qtlsVitbe3E4lEMDpRq9XDw8MVFRVNTU10On1mZobBYAwODlKpVENOhMXFxc7OThQKNTs7C/QesLy8PDg4WFdX19DQMDo6CiYqQaKBiYkJsD+3pqYGhUKBvvz09DSZTO7s7KRQKHw+n06n9/T0gEV+oVBIJpMbGxubmpooFAqIL+/u7u7o6GhtbQXjEqj3a8MAACAASURBVDqdDiIm6HR6Y2NjfX19R0dHe3s7Go3G4/EgJwIWi62rq2tqagJb9zEYDIlEYjAYIMEB2EukUChAiDwKhZqammKxWMXFxe7u7k5OTkVFRTwej81m43A4Op0Olkw2NzeHh4dra2ubm5tHR0fn5+cZDEZjY2NVVRWBQJidnZ2dne3r66uurm5vbyeTyWBhz7BIOTc3h0ajy8vLm5ubKRTK7Owsg8EA+QgMsj05OYnD4Wg0mlQq3TvZC/FOASnNuwXI2MFms9va2goKCuBwOAaD4fP5YEAwPz8/MDAAkpdMTk7KZDKdTqdSqYRC4eDgYE9Pz8TExObmplKp5HA4w8PDJBKpv79/YmJCoVCATTOGDCjDw8OLi4tbW1sCgYBIJJJIJD6fv7Gxsb29vb6+PjU1RaFQGAzG3p3b6+vrXC53fHycTqdzOJy1tTUQUKDT6WQy2fz8/Ozs7MzMDIfD4XK5QqFwaWkJpM+Zm5tbW1sDSqPX60EqF6VSqVarpVIp2IwpEAjW19fX19fn5+d5PN7y8vLemGCZTLa4uLg3S4pWq11dXaXT6QQCYWhoaGZmRi6X63Q6tVq9vr7O4/EmJia4XC6Qw+3t7dXV1fn5eT6fz+fzBQLBwsKCVCrVaDQ7Ozubm5sKhQIESSuVSo1Go9PpwMaalZUVqVRqaNQ0Gs3GxgaIcNNqtdvb20Crtra2pFIpkHOVSrWxsfHm0vTu7i7QEkO+FtBLAAWqVCqDDoHz1Wr12tqaSCRSKBRgCQcEsoPPFyw4vbaTX6vVymQymUxmeNX6/zfh2Gvli8XitbW1N+O1DJXU6XSgzm9+UcEYF+y0BfECJBLJkDvg7019Zng5P/lXvV6/tyZ/62QoD827DKQ07yJg68z4+DiLxVpcXATN1s7OjkKhALMK6+vrMplse3sbNEAKhWJlZWVlZUUul4PGDrQ4crl8fX1dLBarVCrQeorFYrFYDNp0pVKp1Wo3NzdBiyaTyVQqFWjUNBqNXC6XSCRbW1uggdBqtVtbW6BN3NjYkMlkGxsbe3/8Ozs7Go1me3tboVAolcrt7W2gjltbW0DAfnJmQ6PRqNVq0MhqtVq1Wq1Sqba3t0Ej/lrb8Wb7IpfLl5eX19bW9rbsGo0G3Bo034bjYFpsa2sLFL6zs/NmgT95UP9TrRgQm9cu/PmPdXcPb5b2k/f9yTJ/Zo4IfBA/X43/tvxfyPr6Og6HKygoKC8vp1Kpq6urr5UGNf0QBiCleW94G7/bX1Lm32ocf/5Pf+vk/2Hd/t5C/rG7/JLTfuGre+2/v9bL/Mf4FQvXaDTLy8sUCqWrq4tGoxmSv72Ne/0k0Jjm/QJSGggIiL+bnZ0dQ0LrvYmlfwZICf6VgZQGAgLiLQIiLP7b06DF/H9uIKWBgPjnQa1W/5Jm/f8bWq1WJBItLi7+TJ6Yzc1NiUSy11oGBHG8Fu8A8V4DKc17j1Kp5PP5TCYTJDbe2zfUaDTz8/M0Gm1sbEwgEBjyDwITMBCaBdYGNjc3QQwCcMEB0WgEAqG3t3dwcNAQ2QWCuJaWlsRi8fb29pv90M3NTS6XCwqZnJwEsQACgWBsbIzBYMzPz4NcZ4ODgyAlIshxsLKyMj09PTs7KxAIuFwusDgbGxsTiUSG9W1gKTY0NDQwMDA5OWlI/g/uODk5uby8DEIkwHGxWMxisUgkEplMXlpaAjEOExMT4MjCwsLelXOpVAqSCwwODg4PD4MtpUwmc3p6msPhADM0MpkM3N4mJiZAtAV4EAKBMDAwMDIyAi7k8/mLi4tjY2N9fX2jo6MCgWB5eRmcSSKRqFQqmUzu7++fmZmRSqV8Pp9AIHR2dvb09JBIJAqFMj4+LhQK9y57KJXK8fFxNBrd29sLUqYCB5fBwUE+nw9C1NhsNo1Go9FoFAoFfHbT09MgfbJEIqHRaFgsFrgGEInEoaEhoVAINgKDrw2VSu3u7u7p6aFSqWw2e2xsjEqlUqnUoaEhYI82MDDQ3d3d39//Wt7VhYUFAoGAx+Pn5uYM1mR6vV6hUPB4PCaTCeKtkUgkGo2m0Wh78/FotVqBQEAgEJqamtBo9OTk5MrKyvj4eHd3d3d39/j4+N5dwxDvO5DSvPeAVFEJCQnPnz9vaWnZ+2MWCARlZWUhISGxsbGdnZ0g1a5er5+amioqKsrLywPuXqDjSSQSS0pKQC6QBw8ePHz40Nvb28fH5/nz583NzWBDzMLCAhaLra6u7u7uBjs9X6sM2AgZFBTk7u6el5c3OTk5Pz+PQqFgMFhhYSEej6fRaKWlpd7e3iEhIW1tbaurq1KptL+/v7y8vL6+vrOzs7GxMS4uzsPDIzY2lkKhGG4xPz8PLvTz8ysrKzOk1xQIBCUlJSkpKSCRmqFHPzY2BoPBPD09IyIiCAQCMNMsKCh4+PBhaGgoDofbu4+Sw+GUl5c/ffo0ODg4KioKbL4pLCysrq4uLi4GZmuxsbFRUVEPHz5MS0sDBqAVFRUBAQHu7u5hYWHp6elJSUkZGRk4HI5IJMbGxtrb28fFxfX09AwNDZWVlfn7+/v6+mZmZqampkZHR7e2ts7MzLS0tLi5uVlZWXl7e4MUD+np6R0dHXsb9IWFBRgMBowVUCjUxsbG8vJySUlJWFhYc3Pz3NxcT09PVlZWWlpaYWFhcXFxXFxcYGBgQUGBQCDY3d1lsVhxcXHm5ubu7u7x8fHe3t5eXl4tLS3AzA0Oh4NLrK2tHR0d09PTKyoq8vLykpKSYmJigoODHz16FBER8fjxYwsLC3d39+7ubkPFNBpNW1ubs7Ozs7NzfX390tISkHmVSjU2NlZdXZ2Tk5OXl1dQUJCSkgLygU5MTBgu39ra6ujo8PPzs7KyioqK6uvro1KpqamplpaWPj4+SCTS8HWF+CcAUpr3HqFQWFtba2NjY2Rk5OvrS6PRwA9+bW2tqanJysrq6NGjjo6OSCTSsJ2wu7vb3t7e1NQUBoPNzMxsb2+LxeLh4eGGhoakpCRbW9vTp0+fP3/e2tra398/IyOjo6MDtCNjY2ORkZEWFhZBQUEYDObNiKOFhYWysjI7O7uLFy8GBAR0dnYODw+Xl5dnZGRUV1dTKBQmk/nixYuTJ09aWFg0NTWBkOv29vb09PSSkhJgnubq6nrs2DF7e3sikWhQDoFAEB0dfeLEiZs3b8LhcJA2Rq/Xj4yMeHh4XLp0KSwsbGBgwDBLQyQSQ0JCrl275uHh0dPTs729zeFw4uLiLl++bGNjg0Qi98okk8mEwWAuLi7Ozs7R0dEIBKK6urqsrKywsDAhIcHLy8vHxycxMdHT0/Obb765fv16Z2cnm83OysoyNzc3NTUNCQlBIBClpaXFxcXASNTBweHQoUMhISHA8To5Ofnq1atWVlavXr2qrKzMzc3F4XCzs7MvX740MTExNTUNCgoKCgoCvpkvX77cm6ZaJBJFRUV99NFHJ06cAD46k5OTOTk5AQEBwKAhMTERVK++vr61tTUhIcHS0tLPz6+vr08ikVAolIcPH+7fv9/FxSUnJ8fCwmL//v1RUVFUKpVAIFRUVBQXF4McCteuXYPBYG1tbQgE4tmzZ66urg4ODr6+vpGRka6url999dWhQ4cQCASolVarnZubS0lJOXXq1NmzZ9PT0zkcjlqtlsvlTCazqKgoJiYmOTm5tra2vb29rq4uOTn55cuXe005t7e3y8vLQb6AmJgYGo1GpVLd3d0/++wza2vr3t7evWniIN53IKV571lbW+vo6Lh///7nn39+4cIFBAIBPLvodHp4ePiXX3758ccfe3l5USgUML+hVCorKyuvXr26f/9+kFME7MIB02JkMhmYYJqbm8fExABjlfn5ebCxhkQiOTk5ffbZZ8ePH09PT3+zLZBIJJ2dnaGhoXfu3HFwcAD2IS0tLUQiUSgUyuVysViclJR0+vTpBw8eDA0NabVaiUSCwWCAsySZTG5vb/fz8zt+/Lirq+vY2JhhNmx9fT02NtbY2NjBwQGDwYDZs52dHZC/58CBA2ZmZqWlpQY1HRwcfP78uYODw9OnT4lEolQqnZiYSEtLu3v3rpeXV19f396pPw6HU1ZWFhwcHBYWVlNTMzMzs7y8zGKxWlpa0tPTnz9/DvKyREZGHjhw4Nq1a+3t7RwOp7i42M3Nzc3NrbCwcGJiQigUCgQCuVzOYDBcXV3PnTv36tUrqVTK4/EyMzNv377t5eWFx+OFQiGfz5dIJOvr63A4/P79+0+fPm1paUEgEFFRUeHh4eXl5SBNNUCtVhcUFIBsOmACrb+/v7W1FaQmi46OdnFxCQ4OxmKxIpFobW2ts7PTx8fHzc0NgUBMTExQKJTw8PArV64kJCR0dXUFBQWdOnUKJLdeWlqanp4eGBhIT0+3tbUNDQ0lk8lra2vAbi4gICAwMDAzM7O0tDQmJubSpUumpqaNjY2gViKRqL29/dGjR6ampnfu3ElMTKTRaMBSAQ6HP378+Pnz5+3t7WC3k0AgAIpr+HTAZ1dVVWVubm5nZ4dEIsGg083N7Ztvvnn69KlIJHqnFpwg/odASvPeA9xWvL29jY2NT5w4ERgYSKFQNjc3BwcHHR0df/Ob33zwwQehoaHAPkChUIyOjubl5Xl6ep4/f97ExCQrK2uvYMhkstLSUltbWzs7u5cvX4JELGBbpUKhGB4ejo6O3r9//wcffODq6joxMfFa6Cow7Hrx4sX169cPHz5sYmISHR1NJBINQw21Wp2RkQFGPGAuRSqVgmyVeDx+YmKir68PmNl4enru7QIrlcrk5OQzZ844OTl1d3fL5fLt7e35+fn29vbk5GSQ5M3Hx8fgIDc6Ogqy6wPLZAKB0NLS8uTJk1u3bvn6+g4MDOytNofDKSkpASmEs7KyaDQa2P3a2dkZGxsbHR2dmpqakJAQHBzs4+OTnZ3NYDBmZmZKS0vd3d3t7OwiIyNBQw9KY7FY7u7uZmZmwDGMz+cnJSVdvXrVwsICDodPTU2BNnR7exsOh1tbW4eGhtbV1ZWUlKSlpSEQCAqF8pq7dktLi42NTWho6PDw8PDwcF1dHYlEAg469+7du3v3bkZGhmGQx2AwwsPD3dzc8vLyiEQiDoeLjY21tLR0dXVNSEiIjY1NTExsa2sDg9StrS0Wi/Xq1auQkJCCggLDI2AwGD8/P3t7+8ePH0dGRkZGRkZHR5eWljIYDJ1OJ5FIBgcHweDpypUrZmZmISEhwMgOg8EAw4LCwkJQJbCgNTIywmazX/PELC8vv3nzpp+fH7CFnp6eBp2GzMzMv/dXAPGOAynNew+Px6usrIyNjQUjiatXr6alpTGZTCKR6OPj86c//enPf/7z06dPwaw3n8+Hw+HPnz/PyMhwc3M7duyYr6+voZHS6/Vyuby0tBRks8/PzwdKo9frQY4cEolUU1Nz7969//iP/7h48WJLS8try7abm5tDQ0NRUVEnT5787W9/+/vf/97Gxqazs9MwVaVSqdLT0y9evOjv7w+s4xUKRW9vb1VVVW9vL4vFwuPxT548OX36tLe3N4fDMZSsUChSUlJOnz5taWnZ0NCwvr4ukUh6enrKy8sbGhqePHny7bffnj9/vq2tDYgfnU5PSUmxtra2trYGrWR2djZIz+zo6IjH4/dWe2xsLDEx0dra+v79+0FBQbW1tSD5TX19fUBAQEhISGBgoImJyd27d+vq6sRisVqtnpiYyMrKsrOzMzc3d3BwSElJoVKpoLTBwUF3d/f79+93dnZub28DB7OLFy+eOXPG19e3tbV1dXUVvIq8vDzgmABsCKKiovB4/GupDfR6fVdXl5+fX0RERFtbG0h5SaPR5ubm0tLSLly4cP/+/draWoNIDA8Pg9Wj0tLSnp6eqqqq58+f37t3b//+/ceOHQsLCxseHjbkrJPJZHg8PjMzMzo6uqamxqBwwHXmwoULN2/evHDhgrW1dWVlJcjfs729zWAwwBDQwsLCxMTkwoULTk5OKBRqaWmpsrLSzMzMwcEBhUKBhEM0Gq2kpCQnJweFQhkStgJevnx59uxZX19f0A0ik8lWVlbHjh3Lzc39u38GEO82kNK893A4nIqKCgQC0dzcHBAQ8M0335w8eTI+Ph4Y2xw/fvyzzz6LiIgAkQJsNjskJMTe3h4YZH311VdmZmbA/AaUJpPJSkpKbG1t7e3tDWMavV6/srKCQqFKSkry8/NtbW0/+eSTffv2RUVFGcYQAJBRMSEh4fr1659++ukf//jHU6dOvXjxwuAysLOzk5qaevbsWR8fHzCmUavV/f39IMpgfHy8v7//2bNn586d8/PzM9i46fV6qVSanJx8+vRpsMCzsbGxvr5eUlISFBQUHx/v7u7+xRdf7N+/PykpaX5+XqvVstnszMxMZ2dnT0/P/Px8EAEVEhJy+vTpe/fu4XC4vdXG4/EBAQEODg4JCQkg+ePa2tr6+nphYaGHhwdY7f/xxx/PnDmDRqPBJWNjYzExMa6ursAnu6OjY25uDixUdHd3BwYGBgYGDgwMyGSyrq6u0NBQJyenwMBAOBw+OjoKEnSqVCrga+fk5JScnOzi4uLi4gLyRr/G4ODgs2fPvL29X7x4kZqaWl5eLhQKFxcXY2Njjx8/bm9vj0ajDZ9gd3e3jY2Ns7Nze3s7yOscHR3t7+9/9uzZw4cPe3t7EwgEwxBzeXm5pqYmJiYmLS0Nh8MZ+g1VVVVmZmbAgM7ExMTY2LikpAT8SS6XI5HIpKSkxMTE2NhYPz8/c3NzGxsbkPn71atXZ86cuXfvHogd0Gg0wGrB3t4+NTUV9C0M5OXlnT17Njg4GHSDcDicvb39jRs3DKtBEP80QErz3sPhcKqrq1tbWwcGBpKSkr777rvf/OY3ly5dKikpaW5uNjMz+/jjjwMDA7lc7sbGBg6H8/b2trKyCg4OdnBw2Ldvn7GxcXJyMpgV0ev1Mpns1atXlpaWd+7cycjIAPNXu7u74+Pj6enpwcHB0dHRDx8+NDIy+uKLL65evVpcXLy+vm5Y85DJZDgcLioq6u7du1evXjU1Nb1y5cq1a9ciIyNHRkbkcvnGxkZ2draJiQnwRQYpNYHXMg6H43A4g4ODwLjFxcWFQqHIZDKQ5nJ2dvbZs2fHjh0zNTUFNlxsNjs2NvbOnTvOzs73798/cuTIN998A0Y8i4uLVCo1Li7O0dHx6dOnwIlydnY2NTX19OnT169fRyKRhjprNJrKysrbt287OztjsViQ7U2r1fL5/IiIiHv37pWUlHR0dLi6ul66dCk9PR0Y0KHR6AcPHjg6OoI5JaFQKJPJlpeXqVQqHA739PQMDw8fGhri8XhwONzDwyM4OLiqqgo4j0kkks3NTR6PFx0dffny5RcvXiCRyEePHt2+fbu4uFipVL42pmEymampqWCgGRMT09fXp1KpVldXYTDYjRs3HB0dKyoqQCS6TCarqKiwsrIC9j/Dw8PPnz/39/d/8eJFbGxsUFAQCOrr7+/XarU6nY7D4aSmpj58+DA+Pp5AIIDd/kACTUxMwsPDMRhMVFSUiYlJZGQkSNU6MTGRn58PpuAGBwfLy8vd3d0tLCwKCgpmZ2dra2vv3Llz9+7dkpKSmZmZmZkZ0HG5efPm8+fPmUwmeKKdnZ3V1dXk5OSLFy8+ffqUz+evr69XVVU5ODjY29s3NTVBGzn/yYCU5r1ncnISgUBUVVX19PQUFBSYmpr++c9/PnnyZHFxcXd3t6Wl5b//+7/b29t3dHSg0ej09PTHjx8nJCQ0NDTAYLCbN29+9913N2/eLCkpAWvsMpksJyfnwoULx48fDwkJATNCGxsbra2tHh4eXl5e5eXlNTU1Pj4+n3/++e9//3tbW1sCgWDw+FpeXi4vL7exsQHOjElJScBt+quvvnJxcamvr5+enq6trbW3t79+/XpAQEBRUVFFRQUwRCGRSEtLSyQSydfXd//+/ZcuXcrKyqqsrHz58iVInu/p6fnpp58eOnQoPDy8qamprKzMw8PD1tY2NTU1JyfHzs7uk08++eijj3x9fQkEQltbm6urK7Ayw+PxarWaw+EAH7ajR48WFhaCVlWn0wmFwqioKGB1ikKhQCuv1WoJBMKdO3cOHz4M6lZYWOjk5GRnZ5eRkYHFYtPS0k6ePHn69On4+PjGxkYQzjA0NFRUVOTs7Hzu3Dl3d/f29nYcDufl5XXq1ClHR0cwgzQwMAD21lRVVbm4uNy8eTM/P394eBgGg92/fz80NLSrq+u1bSuzs7PFxcWOjo53795NS0sDs52bm5tdXV2RkZFubm5hYWFwOLyurg6BQLx48SIkJKS6unpmZqazs/PBgwc3b94MCwsDRtGBgYF37tzJysri8/kymYxEIvn7+1+6dOnBgwcgFHB3d5fL5T569OjYsWOhoaGjo6NtbW0BAQFeXl5paWk1NTXl5eUgRILFYolEoo6ODjc3t3PnzoWHh1MolIGBgYSEhAcPHnh7e8fFxSUnJ3t6eoIYa2BUAZ5ILBbj8Xhvb+/Tp0+HhoZSKJTBwcHo6Ojr16/fv3+/oaFh7+4ciH8CIKV519HpdD+fJ3hmZqaurq6srKy9vb25uRl0UQMDA1EoVH9/v7e39+HDhx8+fFhSUpKRkREZGQmDwQYHB8Vi8fj4eEJCwuXLl69evQq66nq9XqFQVFRUWFtbg7jh0dFRvV4vFosrKiq8vLySkpKmpqbW19cbGxuBh/S9e/eam5sNiwRLS0sIBMLBweHSpUuhoaEEAgGDwbi4uHz99dfGxsZJSUlgd2FWVpaLiwswhQQtY2ZmJpvN3tjYGB0djYmJAd7MUVFR0dHRjx49ysvLa25ufvr06dmzZ69cuRISEpKXl5eZmRkSEpKRkQHMpOFw+JUrV/bv3+/l5QVMbry9va9evert7d3X1yeXy6lUamho6KlTp0CUGphO1Gq1U1NTsbGx58+fv3v3bkNDAzi+tbWFwWCAK11cXBzYy5mfn//gwQN/f//i4uLk5OQbN27cuHHj6dOnycnJqampzc3NPT09ubm5dnZ2165de/z4MQqFQqFQ3t7ely9fdnd3T0hIyM7OrqysRCKRjY2NMBgMLAK1trZOTU319PSkpaVFRUWVl5cbJi0BKysrOBwuJSUlNjYWrH/o9frd3d2lpaXu7u6UlJTQ0NAXL14kJiY+e/YsOTm5paWFx+OJRKLOzs5Hjx7Z2dnFx8dTqdS5ubmCggJXV9e0tDSgE0QiMTo6+t69e97e3g0NDWtra7u7uwwGA4xK4+LixsbGOBxOS0tLQkLCkydP4uPjs7Ozc3Nz0Wi0SCRSKpUkEikyMtLW1vb58+dkMnlxcXFwcBAGgz18+NDFxeXhw4dubm4hISHl5eVMJtOwd3hxcRGJRAYFBTk5OaWnpxMIhPb29mfPntnb2wcFBXV2dv5MTgGI9xFIaf5xfjL57q+bRhCk+pfJZCDI+CfPWV5eHhgYwGKxg4ODdDp9dHS0u7sbg8EwmcyJiYmqqqr4+Hg4HA7iYsvLy7FYrEFUent7MzIykpOTDbttVCoVjUYrKytLS0urra3lcrk6nU4sFuNwuOLi4s7OTjAUEAqFbW1tL1++BLFSEokEVE+hUNDp9IaGhqKioq6uLpFIJBKJMBhMZmZmdnZ2d3e3UChcW1tjMpnt7e2VlZUVFRX19fUtLS1DQ0PAfmZpaYlIJDY0NDQ2NmKxWCQSWVNT09PTw2Qy+/r6KioqqqqqMBhMf38/Ho9Ho9EUCgVs65menq6rq8vPz0cikVNTU2w2u6Ojo6KioqOjg8fjbW1tCYVCLBZbVlZWX18/NjYG/G92dnZWVlbweDwCgWhoaGAymaAd12g0HA6nubm5vLwcj8cvLS3JZDI2m93a2trU1ARSA1RXV1dVVWGxWLCtfWxsDOQCqK+vr6iowGKxU1NTExMTKBQKgUC0tbX19fURCAQymcxkMsfGxohEIgaDAYZgEolkaWmJRqOBnfwgZMAAqDzIL8Dn8/dmbRGJRCMjIxgMBvjOtbe3k0ik+fl5jUaztbU1PT2NxWKbm5tJJNL6+rparR4fH29rawPDR4VCMTc3RyAQwJiMxWKB9n1hYaGvrw9cBYyChELh0NBQR0cHFovt7+8HuQ+Ax4RQKCQQCK2trXg8fn5+XqVSSaVSOp2ORCKrq6vr6+ubm5vxePzMzAxwewO/EZlMNj4+3tXV1dHRMTg4yGazKRQKCoVqaGjo6en5yU3BEO81kNL84xiURqvVAnOqNy1V/ofs7OyIxeLFxUWJRPK3hjWbm5uLi4s8Hg+4ewF/F4VCIZVKwVaG6enpqakpDocD/uXxeBKJZGdnR61WLy8vczgcDodjyEwFfL1WVlZAbhiFQgGy9i4sLMzMzBjMcgzV29raUiqVKpXK8ODA3sbgGGY4U6vV7h2c7e7uAteylZWVvTmv9qbWB5UBrl8GozDg46LT6TQazebm5t677P6Xeddr7C1w739fOw4wPN1rJRgOgqfYy87OzpsHDfX8eV7rr7x2u738jN2AoQ6vveHdN9zM9lbpzcd/rQ577whU+U0fnb2F7D2+97W82Rvb3eMLB8IoxGKxVCo15BP6dX9HEP/rQErzK6BUKicnJxkMxmtd0f85Ozs76+vrQqHQYDf55i9Qp9Op1eqtrS1gd/bacfBTB/Zlm5ubwGQM2EqCtkOr1QINeG0VWqfTgUXj3f/yKFOr1cAn7c166qD1W4j/AUCW/rdrAfEWgZTmV0ChUDCZTAqF8qtnatLpdAqFYn19fe/Mw697CwgICIi3DaQ0vwIgn+7KyophwfPXAsxEqVQqjUYDaQwEBMR7CqQ0EBAQEBBvF0hpICAgICDeLpDSQEBAQEC8XSClgXjX+VvRvRAQEO8LkNJAvOsY9otAegMB8Z4CKQ3Euw4IwAPbgCCxgYB4H4GUBuJdZ3d3V6lUisVipVIJbRGFgHgfj6/H9gAAIABJREFUgZQG4l1Hp9MZvAMgpYGAeB+BlAbiXUf3X2lGNzc3odkzCIj3EUhpIN51DBEB0IAGAuI9BVIaCAgICIi3C6Q0EBAQEBBvF0hpICAgICDeLpDSQEBAQEC8XSClgYCAgIB4u0BKAwEBAQHxdoGUBuJ13sxo+TO7WP7Wn/7bjS+7e/h7r32v+SVP91bfwD/364V4N4GU5l+d7e3ttbU1kUikUCjUarVOp/tJpdFqtdvb29vb21qtVqfTgdN+vmStVruxsSGVSqVSqUwmk8vlcrlcqVSqVCqDU/Xf4i0+8P+LSqUSi8Xr6+sbGxtarfYfKEGj0WxtbSkUCplMplQqNRoNOA4eRKvVgm2nYOfpL8wTuru7u7Ozo1arwSfyD9QKoFarRSIRl8vlcrmLi4tyufzN3HE6nW5jY2NtbU0ikRgqDwHx6wIpzb80Wq2Wz+eTSKSenp6xsbGlpSWVSvWTZyoUirm5OT6fL5VKNzc3lUrl9vb2z5S8u7srlUonJycHBwdJJNLQ0NDo6CiNRhsfH19YWNh7LWhVVSrV1taWSqXa2dn5lR/yZ1lZWRkaGiIQCFNTU3K5/O9t1kFOtpmZGQqFMjIywuPxNjY2dnZ2Njc35XK5Wq3e2NiYnZ0dGRkZGxubn5//+Ze2l83NzeXlZZFI9Lc+kV/C4uJiX19fRUUFAoFAoVAMBkMsFr+mNBqNZmZmpru7m0QiicXif/heEBA/A6Q0/7rI5XI2m00ikTo7OxEIRGlpKR6P/1ttzeLiIg6H6+7u5nA4S0tLPB5vfn5eJpP95DgAdJOnp6c7Ojry8vKSk5Ozs7PLysoQCERNTU1/f//a2tre81Uq1erq6vz8/Orq6v/nbvXS0lJ7ezsCgcDhcAKB4B9QGplMhkaj09PTKysrZ2dnVSqVRCIZHR0dGBhYXl6WSCRDQ0MNDQ0dHR2Tk5O/XDakUimTyWSxWBsbG3//Y+klEgmHwxkYGMBgMA0NDVVVVRUVFWg0msfjvXbmzs4OmUzOyMgoLi5eWVn5B+4FAfHfAinNvy50Or2oqKi2tpZCoTQ3NyclJVVWVgoEgp88eWpqqqSkBA6HDwwMjI+Pk0ikgYGBmZkZuVz+5slarVYkElEolOrq6sjISFdXV19f36SkpPT09KysrJaWltnZWYOi6HS6tbU1NptNJpPZbLZMJnuLz/wGfD6/sbExJyenrq5ufHz8HxhAbGxsvHr1ytHRMSsrSyQS7e7ujo+PZ2dnp6Wl0Wi01dXVrq4uOByOQqFmZ2fVavUvLHZxcbGnpwePx7+myr8QJpNZWlpaWlo6PDw8Pz8/Ozvb29uLQqFYLNabajo4OBgeHh4fHz8zM/MP3OvngYzsIPSQ0vzLsrm52dTU5OXllZaWNjMzw+Vy0Wh0b28vj8cTiURra2tKpVIulwsEAjBjRqfTs7OzMzIyuru7iURifX09EolkMBgikWh9fZ3H401OTs7NzUmlUo1Go9Vq19bWJiYm+vr6YDCYh4eHj49PdnZ2TU1NY2MjDocbGxvjcDhTU1MMBmN0dJRAIGCxWAwGQyAQwJ+4XK5IJJLL5QsLC5OTkysrKxqNRiQSDQ8Po9FoEokkEAjAX1ksFp1OHxwcxOFwIyMj6+vr4AHX1tYYDAYejwdN7WvNq06nE4vFTCazoqIiLCwsJCQEDoePjIwsLi5OT08PDw/39/ez2ey1tTWZTDY7Ozs0NEQikXp7e7FY7MjIiEQiMRSlUqkKCgpsbGwyMzNFIpFUKm1qanJwcHBxccHhcPPz83V1dVlZWX19faurq1KplM/nj4+PM5nMmZkZHo83NTVFpVLxeDwGgyGRSFwuVyqVisViKpVaXV1dX19Pp9NnZmZoNBqRSMTj8f39/SwWC4wmxWLx+Pj40NDQwMDA0NAQnU7ncrlgDpBEIoWFhQUFBTU3N3O53NXV1bm5OXBToVA4MTFBpVLpdPrCwoJKpaJQKI8fP3Z3dy8vL8disd3d3Ww2G6yrzc7OUqlUCoXCYDAEAoFEIllYWACTgRKJBMwNjo2NMZlMKpVKo9EWFhbkcjmXy6VQKBwOR6lUQkoDoYeU5l+T3d3d1dXV0tJSW1vb0NBQMpkM0vKvrKxwudz+/v6+vr6ZmZnZ2dnW1tb/y957BjWWnYnfW7W1W7Vf1+Xa2v2wVVNll8ubah3K9nrHqT3j8Yx7gnvcPZ0TnZuGJuckRA4SCAUQCAmUkFBAEpIASSChLISEUAAFFEEIEEkghBDwfji1Kt4eh/a42/+x+/4+dNHSveece+7Vee7znCcMDQ3ZbDaTyYTD4bq6usBq29PTw2AwwMqlUqmGhoYGBwfFYrHb7d7b2zs5OTk8PARFZaamphoaGmAwGIfDWVhYWF5eDgQCBoOBxWJhMJj29nY0Go3H4ykUCofDGRkZGR4eJpPJdDpdpVK53e6pqan+/n6wZKtUqsbGxgcPHpSXl3O5XIPBwOPxsFgsCoWqqqp68uRJfX29Wq2OxWKbm5s6na6np6e0tBQOh/P5/JWVlfR6l0qlNjY2wAEZGRnnzp27cuUKGo3W6XRzc3NcLhcOhz9//hyBQBgMBrfbTaPRioqKSkpK8vLy7t69C4fDTSZTejKTySSHwykpKcHj8TabbXZ2FolEfvjhh9evXx8dHZ2fn0ej0W1tbWazeWdnx2Kx0Ol0oPFgsVgqlUomk9va2nJych48eFBRUUGn041G4/z8vFAoRKFQGAxmZGSETqfX19cXFBSUlJSUlJR0dHSYTKbt7W2j0YjFYuvr62tqaoqKiurr69lsdiAQSCaTRqMRBoNlZGRUVFT09fVJJJLFxcVwOBwIBDQaDZVKbW5uhsPhXC53dXXVbDbn5eV9+OGHjx8/fvz48b179/B4vNPp9Hq9AoEAiUTW1NTU19czGAygztbV1bW1tTkcjmAwSKPREAhEX19fe3t7fX39xMSE3+8fGRmpqakhk8nBYPDPvPEG8eUEkjRvIicnJ5ubmzweLzs7+969ew0NDUQikcfjzc/Pz83N9fX1tbS0KJVKi8XS1tZWVVWlUCjm5uYIBEJPT8/U1BSfz0cgEBQKRafTCQSC5ubm2tpaAoEwOTnp8/n29/fP9uV0OvF4fGdnp1wuj8Vip6enqVTKbDa3tbXdv3//+fPnHR0dJBKJTCaTSCQSiTQ4OIjBYFpaWoaHh61W6/j4eENDAwKB4HA4NBqtsbGxpKSksrKypaUFgUDU1NSUl5fD4fCioqI7d+5kZ2fj8XiRSDQ6OspgMLq7u+vr6ysrK5ubmzkcjtfrBUPa3NxUKpU0Gq23t7e0tPTixYt37tzB4XA6nc5isYyPj9fW1r7//vsXL15ksVgWi6WhoeHChQsFBQXV1dVXr159+PDhyMhINBoFe1Rgn4NAIFCpVKlUyuVy6+vr7927V1hYODIyMj4+XldXh0KhlpaWQqHQwMBAaWlpQUHBlStX3n///aysLBQKVV1dnZGRkZmZWVNT09zcTKFQNBqNWCxuaGiAw+FUKhWNRt+/f//x48e1tbWZmZn37t2j0+kul4vP58Ph8I6OjqampgsXLnz66acEAiEcDh8dHa2srIhEotbWVqCxwWAwPB4vFouBEslkMvPz8z/++OOysjKgYJWUlFy5cqWioqKoqOjmzZu1tbUKhcLhcIyPjyMQiPv373/yySdFRUVyuVwmk2VlZeXl5ZnN5sXFxebm5vLychKJBK56cHDQ5XINDAzcu3evtbV1cXER8meDOIUkzRvL0dGRzWbr6+vLzc29cePGu+++e+HCBRwONz4+XlVV9fDhw7GxMbvdDpa28fFxq9VKJBLxeLxcLufz+a2trUQiUSqVYrHYJ0+eVFZWjoyMGI1Gn8/3wg62w+HA4XAIBEImk6WNTm63u6mp6fr16zAYTCqV6vV6Lpfb2dmJw+FEIhGHw2lqasJisSqVSq1W9/X1lZeXl5eXY7FYqVQ6Pz8vkUhqamouX76ckZHR0NAAHA26u7uBzCsoKCgoKMDhcNPT07Ozs8PDwwUFBTk5OSKRCPS+tLSEw+FQKJRWq52ZmcFisTAYDDhEWK1Wt9vN4/E+++yzn/70p0Qi0W6319fX37p1i8FgGAyGrq6ukpISIpFos9ni8fjp6enJycnS0pJIJCISiT09PTgcDofDdXd39/X1kUikzs7OqqoqGo22vLys1Wrz8vIePnzY1NR07969H/zgBw8fPhwaGurr62ttbeXz+VKptKmpqampyWAwGI1GOBxeVlbG5XLJZDK4Iq1Wi0ajb9y40dnZaTQah4aG2tvbJycnwep/+/ZtsVh8eHgIdMq1tTWDwUCj0ZqbmwsLC2/dupWZmUmhUGw2m8ViQSAQv/zlL+/cuQPMbqWlpYWFhXK5XK/Xd3d3d3R0gBtqMpnGxsZgMNh777137dq18fFxu93e0dEBh8PVarVOp0Mikf39/UBXe/r0KYlE8vl8bDY7OzsbiUT+UU4QEH/FQJLmTQTYkba2tubm5kZHR7u6um7evHn+/HkYDEYike7du3fp0qWJiYmlpaXKysqbN2+CneSBgYG+vj6lUikSiRAIBFBimExmY2Njc3MzHo8nEokCgcDn853ty2q1otHo1tbW8fHxcDgMPtzY2MBisZmZmQMDAysrK2DbvLW1taenx2QyqdXqmpqazMzMrq6uycnJyclJsDQjEIhAIHB6ehqJRGpra3/84x//5je/6ezslEqls7OzcrmcTCbD4fCrV69++umnbW1tHo/n9PTUaDQ+fvz4/fff7+vrSw+pqqqqsbExFAodHh6KRCIUCjUwMDA8PCwUCq1Wq1KpfPTo0TvvvEMmk5eWltrb27OysvR6/f7+/vj4eHNzc29vr06nS8vUnZ0dg8EAg8GuXr1aUlIyNjY2Pz8/Pj5eWlp69erViooKtVodjUa5XO5vfvObu3fvcjgcIE0HBgYUCgWNRuvv719cXPR6vU1NTWVlZXNzcy6XCw6HFxYWisXi0dHR5uZmsVgcjUaZTOadO3fQaPT8/PzQ0BAMBmOxWMAgNjQ0tLy8DIZ0cHCwtbUVDoc9Ho9Wq2WxWE+fPv3ggw+ePXvG5XIXFhY4HM7Vq1fv3r2r0+nMZnN+fn5FRYXf7z84OJBKpQQCgUKh0Ol0Pp+v0+lYLNbly5fPnz/P4/E2NzelUikSiezp6QFOByaTaW9vTygUZmVlkcnk1dXVkZGRp0+ftra22u12SNJAnEKS5s3k+PgYxPQtLi4uLS05nU4mk1lbW4vFYvv7++/evfvZZ59xOByDwZCfn//ZZ5/R6XSNRtPd3Y1GoyUSCZfLbWpq6urqkkgkKpWKzWYjkci8vLx79+7V19fPzMyc7ctms6HRaBgMRqPRFhYWgMVpe3t7YGCgoqJCKBTGYrG1tTUej9fQ0NDf3+/xeKxWa01NzUcfffTw4UMOh+PxePh8fklJSXt7u9VqPTw8DAQC7e3tn3zyybVr1xAIhEQisVgsOp2Ow+EgkcinT5/evXu3ra1Nr9eHw2G5XP78+fMrV67QaDQwJLvdXlNTU1VVNTMz4/F4KBRKW1tbb28vFotFIBBDQ0NMJvPp06cXL16k0+kOhwOJRBYUFIBwE6lU2tHR0d3dPT09nfa7Oz4+drlcubm5//M//5OXl+dyuZLJpMFguH///jvvvNPe3h4KhYALxpUrVx49eiSTyVZXVwOBwNLSklarxeFwaDTaarV6vd729vbS0lKVSmUymaqrq/Py8jgcDpfLbW9vF4vF4XCYzWbn5OTQaDSPx0Oj0e7du/fs2TMsFisUCu12O7BPnp6ehsNho9E4Nze3trYWjUaDwSCVSn369OmVK1eqqqrGxsZGR0fz8vLy8/M1Go1SqXz+/HlJSYndbt/e3pbL5TQajUgkwmCwqqoqgUAwOTn5/PnzS5cucTgcMP99fX3Z2dmlpaUCgSAWi6VSKdAgkUh0OBxkMvnBgwd1dXUzMzPpIUG8yUCS5k3k5ORkd3d3ZmaGSqUymUyJREKhUJBIJJvNHh8fr6iouHTpUk1NTWdn582bN69cuQL2/6uqqiorKwcGBtBo9PPnz8vKykgk0tDQEBqNrqioePTo0d27d5uams7ulp+enjocDjQa/ezZs4qKCrFYDNYdn8/X1dVVVFTE5/PX1tYsFgsajS4sLOzt7QXebsBG9PTpU/AS7fV6aTQaMNRwOJzR0VE8Hl9WVvb8+fOamprBwUGFQqHRaNhsdmtra1VVVVNTEwqFwmKxPT09XV1ddXV1XV1dRqMRDMnlcrW2tj579qy5uRmDwdTW1tbU1CAQiNbWVhgM1tTUVFdXl5GRcevWrZ6eHqFQCCxyfD5/cXFxYmKio6OjpaWFx+Od9T9eX19vb2+/fv16V1cX0HU8Hg8MBnv69KlAIAARqZOTk0VFRdnZ2SQSSa/X2+12sPPf2NjY0tIyOzvr9/u7u7uLioooFAqDwcjLy3v69Ckaje7s7CwtLR0aGvJ4PGNjY01NTcDxD4vFfvjhh+fOnbt+/XpZWdnAwIBer49Go8fHx0tLSyMjI0NDQwqFQqfTAfe2wcHB8vLygoICNBrd399fUVFRXV3NZrPpdHpBQUFtba1Wqw0Ggzqdjs/nEwiEoqKizMxMNBpNp9PLy8tzcnJGR0ePjo6Ojo7Gx8efP39eXFxsMBjADExPTzc0NLS2ttJotI6OjuLi4qamprGxsbSaBfEmA0maN5SdnR2ZTFZXV1daWopAINrb27FYrF6v9/l8HA6noKAgLy+vtLT02bNn5eXlZDKZQqHA4XA4HE4gEICQqKmpAet4TU1NTU1Na2sr2GUBBq40fr+fwWCUlJQUFRVxOJytra3T01O73Y7FYuFwuFAo9Pl8SqWys7MTBoMxGIyVlZWVlRUWi9XY2NjT02MwGEASl8XFRRqN1tDQUFdX19fXNzo6KhAIenp62tvbCQSCVCo1Go1isbi7u3twcFAqlbJYLDgcnpOTU1dXx2KxFhYW0q4K4XB4eHi4rKwsOzu7sLCwtra2s7Ozt7cXhK+i0ei6urqioqKqqioCgUCn09vb29va2kZHRy0Wi0qlolAoXV1dQEamL/Pg4EClUjGZTIPBAIyT0WhUJpONjo6mPRHcbjfYWens7CQQCEwmUyQS8Xg8DAYD/NYikYhQKEQikX19fQQCAYhA4LpWU1MzPDy8tLRkNps5HM74+LhMJmtpabl27dqVK1euXr16/vz5GzduYLHYxcXFRCIRCoWEQmF/f//g4CCJRAKbTE6nUyaTAe2tp6cHeP3R6XQymYzFYmk0msFg8Pl8i4uLWq12ZGQEh8O1t7djMJje3l40Gg0E5MHBwfHxscViQaFQOBwuHQrqdrvZbHZnZ2dHRwcej6dSqVQqVSwWpy8f4k0GkjRvHGAdPDg4WFhYEAgEYL2TSCRarXZ1dTWRSHi93omJCS6XOzIywufz5XK52Ww2Go1SqVQqlep0OrBVI5FI1Gr15OSkUCicmJjQ6XRWqzUQCAAv5zQgE8HY2JhAIJibm9vf3z85OVlZWdFoNJOTkwsLC+vr6y6XC0Sr2O32g4ODlZUVHo8HfNsikQhwk43H4zabTSwW83g8pVLp8XhCodD8/LxSqdTpdIuLi8vLyy6Xy2Aw2Gy21dXVxcVFkUhEp9PHxsbOBoqenJzs7e0B7YTBYLBYLIlEApLlzM3NWSwWrVYrkUjGx8flcrnBYJiZmVEqlRqNxuFwhEKhQCBgsVg0Gg0wVaU9p4+Pjzc2NkKhEIg8Te/Jn00nE4vFPB6PTqebmpqamprSaDRzc3NWqxXoHJFIZH9/H9jTNBqNRqMBh6lUqsnJSWAhjEajYLqMRqNIJOrq6mptbSWTyYODg6WlpU+ePEEgEMBgtbu7u7CwoNVqVSqVQqHQarXLy8uJRGJ9fd1isajVao1GA8JiZmdnQaIg4LUcjUY3NzdXVlYWFxdNJpNOp1Or1Wq1emZmZmFhIRKJxOPxaDRqNpu5XK5UKk0HMIGrU6lUMpkMSDW73b6wsLCxsQHF00BAkuaNIy0Djo6ODg8PE4nE4eEhCLcEK8Lx8TH4Kv05IJlMgv8m//+Aw1KpVDrz5gukUilwGMjOCT4BbYKzwAHgmL29PbPZTKPR+Hw+CLlPjxwknUwkEslk8ne1A/5OZ6gEV3c2bBMM6fj4OJlMJhIJ0Fq6EdBC+krPAr4928vZNKMv5Ab9fKrQdL/p2XihC9AamPyzA0jPM7hBJycnyWQyFApNT09TqdTh4eHZ2Vmbzcbj8fB4PJvNnp+fByIQXGO6r/QknJ20z09gehip/wOMAXx1dHQEXNomJiZUKtXS0tJZp/b0kwMuJz1jkKSBgCQNxJeIRCJht9vZbHZfX59UKoU2k38X8Xh8cXGRy+WCoFc2m02lUrlcrtlsXl9ff/mcN1+gX4vFApwmgJ83FJgJ8TJAkgbiSwSI7Wez2SMjI2az+Ysll3xD2NraUqlUBAKho6MDg8EMDg4qlcq0Let1APJzm0wmNpstFouhrX6IlweSNBBfIuLxeCgUAnlQ0kH4EL+VVCoViUSsVqter5+ZmQG7U69Vwzg5OTk4OFhdXXW5XH6/HwSuQkC8DJCkebNIF4PZ3d0FFcC2trb29vb29/d3d3e3trY2Nzd3d3dfiLbb3d1dXl4OBoPr6+vxeDxt8Qf73ru7u+AsEJ0OCqDt7Oz8ntpi6V2iVytL0rsvYCR/SjsgedoLdXT29/fX19dXV1e3t7f/xC5eIJVKHRwc7O/vpz0XDg8PQRG5F+4FmN6Xr3Pz8pycnICSB5FIZHt7GzKLQbxCIEnzZpFMJqPRKKjcBcLvgbPW/Py8VquVy+XT09N6vd7j8aQtV4eHhyDvJIPBkMlkHo8nvQmcSqVA+IVcLrdYLBsbG6Ayjcvl0ul08/PzwKf586RSKeDgtL29/QrX60QisbGxsby8vLa29qe8cScSCYvFIpFIrFZrek1PZ53hcDhGoxGErbyigZ/u7+/7/X6QyBl8AtI5q9Vqt9t91sktEomARKWvfJsd7ParVCoOh6PRaCDTJcQrBJI0bxbb29uzs7MsFquvr6+/v394eFgsFotEIjKZ3NXVhcPhQH1GFotlNBoDgYDT6ZydnQUOwWQyeXh4WC6X+3w+oIskk0mFQtHV1YVGo6empiKRCJA0MzMzFAqFy+X+LlP+0dGR3+8HBp9XeHXAQ9rj8Xi93kAgEA6HNzY29vf3/1iRAHKr1NfXo1AojUazu7sLPp+dnW1vb29oaJBKpb9LiH4x9vf3HQ6H2WxOT8jGxoZGoxkaGmIwGLOzswcHB4eHh8A7fHp6+nUEqRwfH0ciERCHRKPRfmvlod9DPB4Ph8Ovdlog/mqAJM2bxfLy8vDwMBwOB9mXJRKJUqlksVgwGCwrK6u+vr6vr6+pqamyspJIJLJYLCQS2d7ePjo6arVarVYrKCRjMpnAm34ikaDRaFlZWbW1tWq1emdnB5jFzGYzBoPp6elxOp2/dRjJZNLhcGg0mle7YsZiMZ/P53Q6FxcXdTrd2NgYiNH5Y6ur7e3tsVisBw8eXLx4sb6+3mKxgM9NJlNdXV1tba1er3+1KYp3d3dBxYG0pEkkEoFAgMFgVFRUEInEUCgUDAbFYjGDwVAqlekMcq+Wg4MDgUBQUVFBIBDO1uB5Gex2O4/H02q1vyvRGeTr/CYDSZo3C5/PRyQSy8rKGhsbR0ZGrFarx+ORyWSglgkMBiMQCGVlZY8ePUKhUN3d3bdu3bp48SKJRIpEIqAWmd1u93g8YDWJx+P9/f337t2Dw+FmszltaHK5XFgstrW1dWpqamlpyWq1qtVqYJdzu92bm5vRaFSn0/F4PJ1O5/P5rFarzWYD2QFASePNzc39/f3l5WWHw2G32/1+/8bGxvr6ut/vdzgcRqMRBGy6XK5AIABK6aysrNhstvHxcYlEAhpvb29vamqi0WhAV/B6vUajUaVSWa3WnZ2dVCoFyrWBmmBLS0tbW1tA+4nH48PDwzdu3PjJT36SkZFBp9NXV1ePjo7sdjvIHLO4uJhKpcLhMKgABkIa9/b2tra23G63Xq9XqVRardZgMLhcrs3Nzc3NTVDNbH5+3u/3r62t+Xw+EJUikUhmZmZMJpNMJpuamjqbYeHo6EgikeTn51dXV0skkrGxMZAYxmazRaPRSCQCIlVlMhnI8BaPxzc2NlwuFygNp1QqQTymXq+Xy+VWqxUkW1tYWPB6vcFgEMhjkPF6ZWUF6Klyubyurg6Px7vd7uXlZRAhGw6HQYG4qakpi8UCtqmCwaDRaNRoNGq1WqVSgZTbGAzGaDQGg8FwOOzz+cxms1KpNBqNa2trkKR5k4EkzZtFKBRiMpktLS0YDEYgEICqi3a7HY/HZ2VlwWCwnp6e4uLiZ8+eDQwMMBiMBw8e/OpXv2poaDAYDMA2Arb6wYq8v79PpVKzsrLa2trm5+fTksbv9xMIBFAumslkIhCI4uLioqIiGAxGJBJnZmbcbrdYLMbhcFwud3x8HIlEtrW1yeVyjUaDQqG6urpmZ2fdbvfo6CgWi8VisWCLSKFQcLlcLBZbXV1dUFAAh8NBAmYikTg0NDQ9Pc3j8VpaWrq6ung8HplMLisry8zMbGhoEAqFMzMzAoGgrq7u6dOnCATC4XBsbW1NTk6CRC8IBGJkZMTpdILVFkiaR48eXb9+PT8/v6mpSSQSra2tLSwstLW1IRAIp9O5vr4+OjoKh8MrKiqwWCzY1NHr9QwGo76+Pj8/v6ioqK6ujkajqdVquVze29tbVVUFipUBT+7CwsIrV648fvwYgUBQqdTe3l4KheJwOM7eL5CftKKiAvTb1dU1PT29trYWCASkUimZTG5ubn727Fl1dTXI5y+TyYhEIgqFKisre/bsWWNj4+DgYH19/ZMnTzAYjFqtFggEfX19AoFgenqayWQCXRah7MIrAAAgAElEQVQGg4lEIrDNplKp6urqWlpagMwWCARqtdpgMNDp9OLi4tu3bzc3N9vt9vX1dZARrri4uLKyEgaD5ebm3rt3r6ioiEQiyeVynU4nFAqbm5vv379fXl6u0+n+/E87xJcHSNK8WYDMWm1tbTAYrL6+HofDKZVKu93OZDJBpq/Ozs6SkpLc3Ny+vj4ej9fZ2VlcXAyDwTo6OnA4HJPJBK/P6QwxNBotJycHgUDYbLa0pAmFQiQSqampiUQidXd3Z2dnP378uLKysqCgID8/n8Vi2e324eHh2tpaBoMhEAgeP35848YNHo+n1+tBWbORkRGxWNzY2Pj8+fPCwsKCgoKioqK2tjYUClVYWHj79u3s7GwYDFZdXV1YWAjqXcrlch6PV1dXV19fTyaTu7u7S0pKCgsLMRiMQqGwWCx8Pj8nJ+dnP/vZvXv3Jicn5+bm4HA4KI5ZW1vLYrGcTie4rr29vaGhoYKCgtbWVgKBUFJSUlNTA1wn0Gg0CoUymUwGg6Gmpub8+fMffvjhkydPGhsbMRgMDofr7e1tbm7OyMi4cuVKWVkZBoNBIBBlZWUPHz48f/78+++/X1tbKxKJ2tvb33333Z/+9KfFxcX9/f1cLjctYs/er2g0qtVqQYMFBQU8Hi8UCsXjcaVS2dHRAYpyFhcX5+TkIJFILBZbWVlZXV2NRqOLiorOnz+flZU1ODgIg8E+/fRTGAw2Pj7e398Ph8OHh4dBmjgYDHbt2rUbN26Ad4W9vb10qRskEsnhcKanp+12O6gZcfv27R/84AcZGRnAJtnd3f3w4cPMzMz6+vqOjo7q6uqsrKyamhoWiwW0t5GRkczMzG9961vnz58XCAR//qcd4uUBdu9EIgF2BF+htwsAkjRvFmtrayKRCAaD3bt37/Lly0+ePBkcHARv4oWFheXl5V1dXU1NTSUlJbW1tSQSSSKRSKVSIpFYVFR069at27dvV1dXT0xMAMekRCIxMDDw5MmT5uZmkM8f9OL3+/v7+zs6Ovh8PkgCjcPhNBoNiUTKysoikUhutxu8IwsEApPJVFZWduPGDSaTOT8/Pzg42N7eTqVScThcTk5OYWFha2trbm7u5cuXS0tLe3p6qqqqCgsLGQzG5ORke3v7w4cPS0tLmUym0WhUKBR9fX0YDGZgYACk7ARixufzBYPBmZmZjo6OixcvPnjwgM/nj42NPX78+L333svNzQVV3bxeL5A0sViMTCZXVFSMjIzMzMwAvYFCoYyNjSGRSDQaPT09zWazHz58+MEHH9y5c6eoqKisrCwvL6+yspLBYIBil9XV1SMjIywWCxSQvnPnzp07dz7++OOGhga5XN7a2vrOO+88e/bMbDavrKx4vV4wZr1ef/Z+pVKpnZ2dvr6+Cxcu5OfnLywsJJPJeDxOJBLz8vIoFIrH49Hr9Xg8vqKi4vbt259++ml1dbVUKgX131AoFCgcV19fD7RYMD+gXs7S0hKHw2loaMjOzi4rK5uYmNjY2BCLxRcvXvz+97///PlzgUCwurq6s7OzurqqUCgaGxsvXrz45MkTgUCg0+lwOFxlZSWBQDAajS6Xi8fjAS3W5/Ntb2+Hw2GlUllTU/OjH/3o448/hiTNl5zj4+ODg4OdnZ2tra1YLPbKQ9kgSfNmEYlERkdH6+vr8/LyCgoKEAjE+Pj4wsICg8EA9ig2mz06OorBYPLz82tqamQy2fLyss1mGx4e7ujoePbs2YMHD/B4PIhFPzw8JJFIjx49amxstNls6V5cLheJRAKloMfHx4FxaXt7WyaTlZSUgIJdNBotNzdXJBKtrq4ymcycnBzg8sTlcnk8HoPBAJau9vb2qakpNpuNQqEoFAqfz0ehUB0dHWazeXNzUyKRtLa2IpFIKpXK5/M5HM7AwAAoEd3W1gaHwxkMxuLiosfjmZ2d1Wq1oNP8/Hwulzs1NYVEIquqqrq7u4lEIpFIVCgUwIF7b2+PQqHU1tbK5XIw7IaGhsrKytLS0tzcXBQKJZPJyGTy48ePs7KyKBSKSCRis9l4PB6NRpPJZA6HQyaTJRJJNBpVq9WffPLJd77znYaGBg6H09/fD0QaAoH4xS9+UV9fD2bs8PCQyWR2dnZqtdrP3zUWi3Xp0qXKykrg2bW3t9fQ0HDjxg02mw3OHR0draio+Oyzzy5dugSDwcRisUKh4PF4c3Nzx8fHm5ubMpkMi8U2Nzc3NzczGAyn07m6umo0GlksFplMbm9vr6ioYLPZkUhkamrq+vXr3/72t2/cuEEkEi0WC8ivCgocFBYW5uXlicVik8kERKNUKgWTptPpOjs7x8bGEonEysqKUqmUSqV9fX2XL1++evXq2NjY63+6Ib44IJoK5GYF2dNfbfuQpHmzWF5e5nK5LS0tYGfC4/Hs7Ozs7+9zudyioqLW1la5XG4ymVgsVlVVVXFxMdg5iEQiKysroGpvXV3dwMAAKM2STCZHRkYqKyvb2tpUKtX6+jqIbZyZmWGxWBwOR61WS6VSUD9mc3NTpVKBMsZLS0v9/f1ZWVkcDmd3d3dpaQmLxWZkZOTm5nK5XLvdPjU1BVQZHA7ndrsjkcjy8rLb7VYqlb29vXg8fm5uLpFI+Hw+kUhEIpEwGExnZyfIYz8wMEAmkzs7O5uamuh0ularlUqlIFUXkUisqamBw+F8Ph+kNB4fHwd1xsrKymg0GnC42t/fZzAYjY2NEonk6OgoFotNTk6Wl5dfuHDh+vXraDRarVbzeLzq6urOzk673Q68FZaWlqRSaWtra2lpKRqNBomrNRrN3bt3QQ2x1dXV5eXlaDS6u7uLRqM/+uijuro6oB1ubW2Bsi4ajebzO+fAwNjY2Ag80/b29jo7O+/fv0+j0ba3t0OhEJ/PR6PRaVtiU1MThUJRqVRgnz+VSvn9/o6Ojlu3blVUVExNTYVCIZPJ1N3dDYfDgWBuampiMpmhUEiv15eWln722WfPnj1raWkBJQYGBgY0Go1CoWhqaoLBYNPT0y6Xi8vl9vT0AE0olUoZDAYcDicWi/1+v0Qi6ejoGBwcpNFoeXl5OTk5k5OTkEfAl5wXctS+2sYhSfNmEQwG6XR6WVlZZWUln89P76yIxeLy8nKgBHA4HBKJ1NfX19PT093dTSaTRSIRKKg1NjbG4XC0Wi3IfZlKpYC6g0ajcTgcnU4H9iIOhyOXy+fm5sxms0Ag6O3tlUqla2trs7Oz3d3dQ0NDMpmssbHx/v37AwMDW1tbR0dH09PTpaWlxcXFCoViZ2fH7/dTKBRQBUckEtnt9uXlZafTKRQK29vbUSiUXq/f3Ny0Wq1MJrO7u7u7uxtUGsbj8QQCgUwmk8lkoKkMDAwMDAwQCAQMBtPY2FhVVYVEIkdHRw0Gw9TUFI/Ho1KpHR0doKglCJ3Z3d1ls9mg3Bm40rW1NSaTmZ+fn5WV1d/fb7PZ9Ho9Go1GIpESiWRhYWF1dXV1dXVqaqqsrOzSpUs5OTmDg4MTExNsNrutra25uZnJZMrlcq1W63Q6A4FAb29vRkZGc3Oz2+3e2NgAThnt7e3T09Nn/adBtgI+n19YWNjY2GixWPb39w8ODiQSCQKB6Onp4fF4w8PDoPYBh8Opq6u7f//+gwcPiouLUSjUyMiIyWTa3d3d2dnp7+9/8OBBR0eH3+/f3d2dnZ1taGh49uwZCoUaHBxEIpF0Oh04sjc3N8Ph8N7e3u7u7paWFlCAjsVigYkiEAgGg8HhcIyNjZFIJBaL5XA49vb2vF7v6Ogol8sViUSgsB4Wi8Xj8c3NzWg0WqPR7OzsQOmF3lggSfNmEQ6HeTxeTU1NcXExlUpNJ2TU6/U4HA4sXqAsmFqttlgsLBarpaUFLDdYLBYoHLFYLL1hmEgkPB4Pm81ubGysrq5uaGhoaWkB9pmdnR2fzycWi4FOE41GPR4Pl8tlMplgHS8rK2MwGKCeWDgcFolEIyMjXq8XbE7q9fqOjo6KigoUCgW2ppVKJai1hcfjjUZjKBSanJzs6enp6+sTCoVGo9FgMIhEouHhYYFAoFQqVSoVg8HAYrFDQ0NisZhMJre2tra1tdHp9OnpaZVKNTw83NvbOzg4yOPx1Gp1MBgES+Hu7q5MJiORSGNjY5FI5PT09Pj4eHV1VS6XUyiU8fHxcDgcCoWAx0R3d7dAINDr9VNTU/39/ZWVldnZ2aCOXFFRERBgoN5lW1sbBoMZGxszm818Ph+JRFIoFKvV6vf7DQYDhUIhkUgzMzNnsxukUqmNjQ2pVAo60mq1W1tbqVQKeAqQyWQEAtHR0SESiYLBoMlkgsPhN2/ezM3NzcnJuXPnTlZWFpFI9Hq9Ozs7YrG4paVFKBQmk8mTk5NQKEQmk4FD8/DwMIVCEQqFs7Oz4MJBBJVSqWQwGGKxeHp6GswklUoFLiR2ux14l/F4PJPJFIvFDg8PgUshnU7n8/lgr4hAIAwNDcnlclDn7XeF2kD81QNJmjeLWCzmcDjGx8eBo1c6DnxlZQUEqSgUiomJCY1Gs7a2BgLXxWIxn88XCARisXhubu7zmfwPDw8XFhbGxsZADmawYIGWd3d3FxcXZ2dnvV7v/v7+9vb24uLi3Nzc7Ozs5OTkxMSExWIBasTR0VE4HA4EAulUN+vr62AtGx8f12q1NpttYWEBxGfodLpQKBSNRu12+/T0tE6nA9EwYJfbarUuLi6Gw+FIJDI/P69QKObm5kC1yqmpKaVSabPZAoGAx+MxGAwKhcJgMHg8ns3NzfQb98HBgdfrNZvNTqdze3s7LVZ3dnZcLpfP5zs4ODg4OHC73dPT01KpdGZmZn5+fmBgoLy8HIVCgUJqBALh+fPn1dXVBoNhbW1Nr9fzeDyRSGQymXw+H6hmZrVal5eX19fXQXdms3l5eflszn+g04Btf4PBAOrBAMsGSKssFosnJiacTmcymVxcXKytrc3Ly6PRaENDQ2VlZVlZWTgcbmFhYXt7W61WE4lEjUYDWo7H41arVaFQ6PX6+fl5i8XidDqDwaDT6ZybmwsGg/F4HGS+AdkWTCaTXC6fn59fXV0Fyd+APRNMZjq+yul06vX6xcXFlZUVu92u1+sdDgc4ZXt7+9WGu0L8BQFJmjeLsyXCwLst+DxdgOuFr0A6TrCwJhKJ32X9+Pxh4PR0sTJg+U3/94XqXumxvVA67GyttrMF2UChrXTdrbNlvtIFuM5WewPHp/s9W37thdPTXZ9t5+xXoN/03+kWtre3aTRaWVkZmUxeWVkJh8N6vR6DwWCxWLvdfnp6mkwmweSAAZwlbR9P10P7/C1L1ys7+y1wS00kEmD/1ul0olAoFAoFUjsDlUIoFFosFofDMTk5KRAIrFZrerMXzMDZqmhpzt4+MCQwk+mJPf4/Xpgl0Ga6GF367xduLsSbBiRpICBeAcfHx3q9Huyuj42NCYVCkUgkEAg0Gs1rrRlzlnA4LBQKgR1sbGxsZGREqVQuLCwolUpQJ81qtYLwzD/PeCAg0kCSBgLi1bC9vW21WkdGRnA4XGdnJ5PJnJubA7ng/jwDiMfjbrdbKpUyGAzge+3z+WKxmFar7evrE4vFf2z+NwiIVwUkaSAgXhl7e3sej0er1apUKpvN9scmqfwTARV0QqGQzWYDW1PxePzk5GR5eXl2dnZpaQnSZiD+XwFJGggICAiI1wskaSAgICAgXi+QpIGAgICAeL1AkgYCAgIC4vUCSRoICAgIiNcLJGkgICAgIF4vkKSBgICAgHi9QJIGAgICAuL1AkkaCAgICIjXCyRpICAgICBeL5CkgYCAgIB4vUCSBgICAgLi9QJJGggICAiI1wskaSAgICAgXi+QpIGAgICAeL1AkgYCAgIC4vUCSRoICAgIiNcLJGkgICAgIF4vr0XSnC2cnkqlUqnU7yml/lu/+oOl109OTo6OjpLJ5NHR0Z+tTjsEBAQExBfgT5U0x8fH+/v7a2trwWAwEokkEonT09OTk5Pd3V2v12swGAwGQzAY/P2NpFKpRCIRj8cPDg6SyeQflBzJZNLtdstkMoVCEQgEUqnUn3gVEBAQEBCvjz9V0uzv7zscDjabjcPhuFzuysoK+NzhcPT39xcWFsJgMIlEcnR09Hsa2d3d9fl8CwsLXq93a2vr+Pj493e6u7vLZDIzMjKys7NlMhkQb2kgFQcCAgLiS8WfKmm2trbYbHZGRsa5c+cKCgpsNhv43Gg0NjQ0XLhw4dq1a3g8fnl5OR6Pp0XIycnJ3t5eNBqNxWKpVMrv94+OjlKp1MnJyUAgAMRSMpnc39/f29tLJBL7+/vr6+uRSGR3d/f09DQWi2EwmO985zvnzp1jsVixWCwej8disf39/cPDQ0jSQEBAQHyp+FMlzcrKChKJ/O53v/uP//iPFy5c0Gg04HOn00kkEh8/fnz79u2GhgaZTGaxWPx+fzweT6VS6+vrJpNJLpc7HI5YLGYymerq6p4/f97X1zc3N7exsbG2tra4uGgymaxWazAY9Pl809PTAoFApVJtbGwcHh4yGIxz58598MEHLBbL7/cvLCzY7fZgMBiLxf6gSgQBAQEB8efki0uaVCq1s7MzPz/f0dFx7ty5f/qnf3r33Xc5HM7+/v7JyUk4HObz+fn5+RcvXnz48GFDQ0NLSwsGg1EoFFarlcfjtba2tre3KxSK7e3t6enpW7du/exnPysoKKDT6UKhcHBwsKGhoaamBo/Hy+VynU5HJpPLysqKioo4HM7GxoZCobh27donn3zS3d0tFAqHhoaEQqHT6dzb24N0GggICIgvFV9c0sTjcYvFwufz+/v7c3Nzf/zjH//85z9vaGiwWq0HBwdra2tsNvvu3bs/+tGPPv3008zMzA8//PCdd96pra0lk8mFhYXnz5+/e/cug8Hw+/08Hu/8+fP/+Z//efPmTTgcXlFRcfHixe9///s///nPCwoKKBQKj8dDoVAXL17893//9/v375tMJr1eDxp/8uRJaWlpSUkJmUz2+/2QQgMBAQHxZeOLS5rd3V0ej1dXV9fS0lJdXf3pp59+73vf+/jjj4lEYiQS2d7e5nK5t2/f/sUvflFQUIBCoT7++OOvf/3rT58+xePxT58+/da3vvW9730vLy+PyWS2tbX9+Mc//sEPfpCbm4tCocrLy995553/+I//uHTpEgqFolAoGAymsrLy3Llzf//3f//222+LxWKdTpeRkfG1r33t29/+9k9+8pNr167R6fR4PP4KpwYCAgIC4pXwBSXN8fGxx+Npa2u7efNmTk5OdXV1RkbGf//3f//rv/7r/fv39Xr92tqaQCB48uTJ1atXCQSCWq0uLi5+++23S0tLuVxufX3922+//S//8i8//OEPc3NzMzMz33777Q8++KClpYXD4eBwuBs3bnz00UdoNHpubo7L5ebm5l67du273/3u3/7t3373u9+lUChCofDq1atf/epXv/rVr7711lu//OUv8Xj8+vo6pNNAQEBAfNn4IpIGhLOQSKTPPvvsV7/6FQwG43A43d3d77333t/93d/927/9W2dnp8FgGB4evnfv3rvvvltZWcnhcCoqKn7961/X1tayWKy2trZ33nnnK1/5yje/+c2HDx/m5OT84he/OHfu3NOnT9va2urq6j766KOf//zn/f39S0tLRCLx3Llz3/jGN77yla/8zd/8zVtvvVVVVdXU1PT2229/5Stfeeutt956662vfe1rn3zyCQaDMRgMsVjslU8TBAQEBMQX5otImng8rlAoKioqPvzww0ePHonF4p2dHafTWVFR8fWvf/0b3/hGXl4ej8djMpmZmZk//OEPP/3005qamvLy8vz8fDQaPTQ0hEQir1+//j//8z8XL17s7Ozs6+vLysr64IMPPvzww4cPH2ZlZb377rtvv/12R0fHzMwMGo3+yU9+8vWvf/2f//mf/+Ef/uG//uu/8vLyCgoKfvrTn/7v//7vjRs3fv3rX3/zm9986623Pvnkk4GBgbW1tVc+TRAQEBAQX5gvImkSiYTVamUwGBgMZmRkBERrJhIJsVhcUlKSlZUFfMzUanV/f39RUVFJSQkOh2MymWNjY1qtVqvVjoyMdHZ21tXVEYlEvV4/Pz/P4/EQCAQMBmtra8NgMLW1tdXV1Vwu12q1ikSipqam0tLSvLy8x48fl5WVEYnEgYGBxsZGBAIxNDQ0MDBQXV396NGj0tJSoVC4tbX1qmcJAgICAuKL80UkzcnJyeHhYSwW29nZ2d/fB1sjiUQiFAqZzWaDwWC321dWVtbW1jwej9Fo1Ol0drs9HA4fHBwkEomdnR2Px2Mymebm5gKBAIjNjEajIE2Aw+FYXFwE/4ZCoY2NjUgkEgqFgsGgx+OxWq02m83v9y8vL/t8Pq/XGwqFVldXV1ZWXC7XwsLC6upqMpl81bMEAQEBAfHFeTUZNo+Pj4+OjkAyzaOjo8PDw/R/k8lkPB5/IWFMIpHY29s7PDz8fFOghbPNvpIRQkBAQED8v+LVSJqTk5PXFC8JhWFCQEB8SfjLXY5e3xL9kry59Wk+P+9/uY/Rn5mXmaiT/+PlT/yzzf9fyo3+Y1eHP2q2/4J4+QsBVpDXFOrwBwugvCR/bJ2UVCp1cHAQj8f/KAPPCw2mUqnDw8NEIpFMJl/JVfyx/FVJmqOjo729vZ2dHZBtE+wkxWKxWCy2tbW1s7OTSCTOZvkEz+Xh4eFrmv2TkxNQEGF/fz+RSPzl/vKTyeTu7u7GxsbW1tbLlHU4/dwq+VsFz+dPSSaTOzs7oKOzKVm/AOD+Hh8fgz9SqVT6v6/2RoCn6CVLJZ0dzB9sOd3awcHB+vp6NBrd29vb3t4Oh8Mg2ywwTUcikZWVlf39/c+fvre3B058wXz95ef4+DiRSCQSiZesCRKPx1dXV91ut8/nA3l4X76j33P7Tk5Otra2gsFgOByOxWKvqhoW2Oo+e3Xb29vBYHBtbe3z4uTg4MDv9y8tLf1R13V6enp4eLi9vR2LxcAzH4vFIpFIJBLZ2dn588cd/vVImkQiEQ6H5+fnNRqNXq+fnZ3V6/VardZgMKhUKrFYPD09HQgEzvoLHB4e7uzsrK2tra2tvY7UnMfHx3t7e8FgcHFxcXl5+S90z+nk5GR7e9toNHI4HKlUur6+/pJngT9SqVQ8HgeZVf/gWdFoVKfTCQSCyclJl8t1cHDwhYcdi8XW19fBcry3t7exsbG9vf3yK9dLkkqlQKLx1dXV7e3t3984eDnd2dnZ2toC6QFfshen08nn8ycnJxcXF1Uq1eDgII1Gm5mZAX40w8PD/f39Vqv1hbNOTk4WFxdFItHk5GQoFPrLKuMUj8eXlpZcLtfOzs4fPPj4+DgQCEilUjKZLBAI/H7/S/ZycnISj8fX19dDodDa2trn5XEqlZqZmRkaGhofHw+Hw69qiUgkEoFAwO12p0MyHA4Hj8dTq9WfT3Syvb2tVCplMtny8vIf1UskEpHL5SqVCrjjbmxsWK1W4If1538Y/kokzcnJSTAYVCgUIyMjNBoNg8F0dHQQCAQqlYrH42EwWGFhYVdX1+zs7NnlPpFIrK+vu91ut9sdjUZfyUiSyeTa2tr6+jq4l3t7ew6HQ61WLy4u/oVKmtPT093dXbFYXFVV1dXVFQqFXv7Eo6OjlZUVq9Xq8Xhe5rU6EokIhcKuri4CgaDRaPb29n7rYb9VLzmrlZ6cnDgcjsnJyYWFhb29Pa/Xq1arbTbb2bfCl9E/fuvnx8fHacUukUj4/X6TyWSxWCKRSPqA36oix2Ixv9/vcDhcLtfGxgZ4Qo6Pj+Px+Oc1EsD+/r7X6xUKhXg8ns/nz87OslisysrKqqoqDocTCAQWFhY6OjoKCgp4PB546T47fovFQqfT+Xy+1+sFUha8vyeTSbBonpycHBwcHBwcgNGmxwycSz/vs5NMJg8PD8G5x8fHu7u7QJyDb+Px+M7Ozt7eHjA0AQ0MNJ5MJoGN4XeljDo4OIhGo+vr6+Cdb21tTSgUMpnMhYUF0GkikTg6OgJGiPQYADs7O1qtFoPBlJaWdnV1ORyO9Hg2NjbSwwMqIKhXsrm5CRpZW1szGo0SiUSv16+vrwO7yMbGxvr6+v7+/sHBgVgsrqurGxgYWF5ePvuAJZNJoHVtbW2FQqGVlZX045pKpWKxGPCJ3d3dBbYNcJf39/dBlUiZTMblcicnJz0eTzgclkgkGAxGJBIBVX57exvoMZFIxOVyMRgMMplss9nA4FdXV8PhcCAQ8Pv90WgUTMXBwcHy8rLT6fT5fNvb28fHxy6XC4VCNTc3K5XKUCg0Nzc3MTEhk8mcTmcikYjFYsFgEBwP7D2bm5vAy3dpaWlhYcHn873CKPi/EkmTSqUMBgORSKRSqVQqNT8///r16w0NDYODg9XV1RcuXPjoo4/KysqmpqbO/qQPDg5WV1ftdrvVav398Z4v//oZCoXYbDaPxwPrzsHBgc1m+0uXNKlUSiaT5eXlweFwr9d79qvfPzPRaFShUAwMDIjF4peJc4pEIlKpFI/HEwgEpVIJ1giwOIKOgLkZODee7TqZTAIzEVi+j46O+Hw+HA7n8/lra2tKpRKDwXC53HA4DI5PJBLAsPCCT/z+/j4wiMfj8c3NTWCwAn2BlSUej0ej0VAotL29DS5QrVaz2eyJiQmfzweKjkej0bW1te3t7RdW6pWVFVD8QqFQ+Hw+sKZsbW05nU6HwwEafAGn00mn0/F4vEgkcjqdHo9nfHwcLB8sFsvn862srHC53KamJiKRaDabz07yyclJIBDQaDRmszkSiWxubq6srASDwWAwGAgEIpHI/v7+5ubmwsKC0+kEv4u9vb3d3d1YLOb1es1ms9frBZcA9MJIJOLxePx+/+7u7tHR0ebmptlsnpiYmJ2dBZPpdDr1er3FYgHzZrfblUqlx+PZ3d0Nh8Nms1mtVjscjs8Lm6OjI4/HMzU1NTExYbPZgNvzV9YAACAASURBVEKDRCJLS0vHx8dXV1e9Xu/S0lI0Go1Go8FgMBQKpRfBRCLhdrt5PF5jY2NOTk5nZ6fdbgdjdjgcMpnMZDKBElY+n89ms5lMJplMJpfLg8Hg/v6+2+0eHh7u6Oig0WhOpzMajc7Pz4+Pj0skEpfLtbu7q1Qq0Wg0j8c7O7fJZHJjYyMQCDidTrlcTiaTh4aGZmdnd3d3gSUD6CjDw8Nzc3NAvHm9XqBSmM1mqVTa29vb0NDQ3t7OZDLlcjmLxerp6ZmengZar0aj6evrw+FwY2Njcrkcj8d3d3drtVq73S4Wi4eGhths9sDAQG9vr0wm29jYOD09DQaDbDa7ubkZhUKBHPl2u72ysvLWrVtIJFIgEAwPD9NoNPAgbWxszM3NUanUtrY2AoGg1+tdLpdEIiEQCEQiEY1G19bWYrHY2dnZV5VM8q9H0phMJhaLJZPJJicnc3Jyzp8/D6oS9PX1PXny5PLly8+ePevp6ZmcnLRYLKFQCLwdAIVDq9W63e6NjY3V1VW/3+/z+dKVqgEnJyf7+/vhcHhpacntdrtcLr/fD15h4vE4sI+53W6/3z8+Pp6bm5ubmysUCj0ej8PhUCgUaVvQ1tbW0tLS4uKix+MJBALp1wer1Wo2m81m8/z8PPhFnRVL4OUxEAjYbDZwjNvtDoVC4XA4FAo5nc75+XmXy7W+vr65uen3+y0Wi8ViAbb7aDTqcrksFovD4VheXl5fX19eXvZ6vR6Px+12g5emaDTq9Xp1Op1MJtPpdH6/H7ymzc3N6fV6m822vLw8Njb2+PHjx48fCwQCq9XqcDhWVlbO7tkcHR2tr68HAgEQSgUuzWKxkEik3Nzc5uZmg8GwuLg4Pz8PyuKtrq46HI5AIAA20tbW1paWlqanp8lkcmdnJx6Pn5qa8nq9drt9amrKZrPt7Oz4/X6NRjM3N7e+vp7uOplMgmvUarWTk5MajWZlZWVnZ6e3t/fXv/41HA7X6/UDAwOPHz+uqqqamJjw+/1gjdDpdGNjYzqdbnl5ORgMGo1GhUIxPT09NTU1OTkJ7trIyAg4ZXNz02QyjY2NTU5OTk5Ojo6OKhQKu91uMBjodHpra2tnZ6dYLHa73V6v12g0yuVyo9H4wuvL0tLS8PBwZ2cnkUhUq9VgxdfpdKOjozweTy6Xu93uF+SxRqOpqalBIBBOpxMUTTeZTGw2u6+vj8fjeb3eg4MDr9fL4/E6OzspFMrZ94CTkxOPxyOTyfR6Pbi/TCZzeHhYIBAwmUwWizU1NSWVSikUCofDWVxcjEQiNptNoVCMj4+z2eyhoSEul6tWq/1+fzAYnJ6eJhKJPT09o6Ojdrs9EAjMzs5yuVwSiUSn0ycmJlQqlVQqpVKpQ0NDi4uLm5ubUqm0u7t7bGzM6XQajUYmk9nd3U2n081m8+bmZvoJ39racjgcEomEwWBQKJTp6emtrS2r1VpQUHDlyhUCgaDT6fh8vlAotNvt4Ael1WrBUxqJRJxOp0wmI5FI9fX1RUVFOBzObrfv7OzYbDYOhzMwMMDlcpVK5dTUFIvFGhwcJBAIKBSqr69PLpfb7XaVStXd3V1WVoZEIpVKpdVq5fP53d3dZDJ5bm4uFov5fD6lUmm3218whwQCgenpaSqVikQi6+rq4HA4BoPRaDSxWGx3d1er1eLxeBQKJRKJgsHgxsaGyWQCLw0sFovNZnd0dBQXF5eXl/f29o6NjQ0NDXV1dQmFQr/fb7VaKRRKbW1tU1PT8PAwl8ttaWlBoVAajUYul9fU1GRnZ7e3tyMQiJqaGhwOp1QqA4GA3W5nMpnFxcUZGRmtra12u31+fr6ysvLy5ctwOJxOp1MoFCqVyufzFQqFUqkEl1lfX9/S0gK+qq2tzcrKqqioKCsre/jwYV5eHo1Gc7lcr2ST769E0pycnESjUb/fD1674HD4rVu3yGTy+vq6x+MRCoU1NTUPHjzIysoqLi6Gw+HDw8M2m83hcEilUg6HIxAIpFIp+HtwcJBKpSoUiheWiZWVlampKSqV2tPTg0Ag+vv7wcuXy+ViMplYLBY80ygU6tKlSx9//HFtbS24f0QiEbzvhEIhnU43MDCAx+MpFAqFQiGRSL29vR0dHfX19VVVVTAYrL6+HovFKhSKs3aew8PDxcVFJpNZX19fVlbW2NjY19dHpVKZTCadTkcgEOXl5V1dXZOTk0qlkkgklpSUlJWV8Xg8l8s1PT2NRCILCwsbGxs5HI5KpRKJRFQqFfzeurq6xsbGzGbzwMDAzZs3f/nLX2ZnZzMYDK1Wy+Fw4HB4Xl4eAoEYHx8fGBj47LPP3n///dLS0rq6OhgMNjIyctaGHovF1Go1nU5nsVg8Hm9wcHBoaGhsbAyNRt+4cSMzM5NEIoFE3Tweb2VlRSKRtLa2Dg8POxyO2dlZgUBAoVDa2try8vJycnJaW1tFIpFarcZisZmZmf39/W63WyAQVFVV9ff3e73e9M9+e3t7ZmYG9AjWGi6XGwqFuru733777du3b9NotJaWlosXL167dq2+vn5oaAjcawwGk52dDcr0MRiMzMzMx48fNzQ0lJeXP3nypLq6uq2t7enTp7m5uTKZzOFwdHZ23rt3r6ysDIVCIRCItra2rq6u7u5uFApVXFz89OnT+vp6JpPJ5/OJRGJra2t/fz94uU6ztLREo9HAXWYwGGq1WiwW9/X1EYnE/v7++vp6JBJpMBjOnqJSqSorKxEIRCAQOD09TaVSNpuNy+USCISRkRGPx3NycpJIJAwGQ11dXX19vdlsPvujkEqlMBgMi8XKZLLu7u5Hjx4VFha2tLQUFhaCdBu1tbWlpaVgtrVaLY/Ha2pqysvLA2fV1dVVVVUJBAKNRlNbW/vee+9duXIFiUQKhUKJRMJkMoeGhkZGRjAYTFFRUUtLC5vNxmKxDQ0Nk5OTKysrYrG4sbGxt7dXJBKx2ezOzs7KysqamhoikTgzM5NWSqxW6/DwMJlMZrFYQ0NDEolkZWXFaDRmZ2dfuHChq6trZGSkpaWls7MTLJE0Go3H45lMJqPRODY2xuVyh4eHiURiW1tbRUUFDoebmZkxmUwEAqGtrY1KpYJXgYqKivLy8tLS0srKyqamJhwOBx7R4eHhnp6empqatrY2sKdFJBI7OjrodLrVagUGtM3NzRfsSIeHhz6fj8lkFhUVFRcX9/X1dXR0ZGZmAvPy3t6eTqcDJi82m63X64FK19TUlJOTQyKRxsfHe3t7a2trkUikRCJxOBwsFquoqKixsVEoFPJ4PAKBQKPR5HK52WweGRkpLy9vbW01m80ymSwjI+Py5csEAkEikZDJZAQCAabIbDY7HI7h4eGHDx8+evRoYmLCbDbX19c/e/aMSqUaDAaZTAbULDQa3dzcTCaTgb4rFou7urqys7OvX7+emZmJQqFoNBoej29qampvbxeJREBn+hP5K5E0Z4lGoygU6vnz53w+H3wSDoe7u7ufPXuWn5+fn5+fnZ3d3NzM5XJlMhmfz6dSqd3d3U1NTWVlZQUFBeXl5QgEQiQSra6unm12fX1do9GQSKTKysqrV6/eu3ePSqWCZDmtra2tra0UCoXP5yORyMuXL//mN79paGig0+kkEqmrq6urq4tKpQoEAiqVisViiUQigUAoKyu7f/9+Tk5OcXFxVlZWbm5uTU1Nbm7u/fv3MRhM2s5z+v+x9+ZfaadZ/vjfMr/MzKlzeqanp3vO9HRVV1dNdVcllVQq+6bGaNzjFnfFXRQRZN9FBAVlEXABAUEBkR2VTdwX3Pc9amLi54d7mq/fJFqpVKp7uk/fH+pYBN7r89znPvfe1+t1enp4eGiz2WpqasLDw8PDw4uKijAYTEZGRnx8fFpa2oMHDz7//POoqKi6ujoqlRoZGfnll1/eu3ePSCS2tbURCIR79+59+umnN2/eRKFQbW1tbW1tbDa7uLj44cOHd+7coVKpZrO5qqrqk08++eSTTxISEohEYl1dHYlEKi4uzs7OJpFIWq2Wy+Xev3//xo0bRUVFqamp33//fXV1dagycXp6urOzo1KpysvL09PTU1NTU1JSsFhsR0dHfX09aAgJBIKioqIbN27QaLRgMCiTydLS0hgMRm9vL5PJLC4uplAoTCazsLAwIyOjtrZWp9NZrdby8vKvvvqqsLDQbrdzudz4+HgKhTI3NxdK029ubvb39zc3N1MoFGB0xWKxExMT9fX1n3322ePHj8ViMYFAiIiIgPWjoKAA5m12dva1a9eSk5NBt+LLL7+8desWBoNJT0+/fPlyZmYmiUQKCwu7efNme3u72+3Oycn505/+lJeX19LS0tLSUllZGR0dnZycjMFgkEhkdnY2BoMBfxcbG3vjxo2cnByTyXQ2xTcxMSEQCDAYDIVCgYCGRqNBdl4mk8XGxt6+fbu1tfXsqLPZbJWVlVQqNVQeGxkZkcvlHA6no6NjYmIi9GFRUVFWVpbVaj37c6lU+uTJEyjqlJeXX79+PTs7m8Vi5efnP3jwIC4uLjc3Ny8vD4VCCQSCrq4ukUhUUFAQGRmJQqHkcnl5efmjR48aGhoMBkN8fPy//uu/hoWF1dXVNTY2MplMHo9nMplGRkY4HM79+/eB7ZBMJsfHx1OpVBDVpdPptbW1tbW1KBSqsLAwMzMzKysLi8X29PSEsoUQjDMYDAqFgkQiGQyG2+12Op15eXlPnjxpbm5Wq9UVFRVoNLqvr89isQgEgvb2dovFwufzKyoq6urqTCaT2WwWiUSw/Le3t/P5/IyMjOzs7ObmZqlUWlVV9ezZs+zsbAjUuFyuSCRiMBhYLJbFYjU0NJBIJC6XC1sfCoUCq293d/d5/S8vXryYm5traWlJS0urrKy02WxKpTIpKam0tBSSBxqNprm5uaWlpbGxsaura2lpaXJyEkaXXC53uVyNjY21tbWtra2wxVcqlTExMZGRkZDOkkqlkG8/PDw0mUxFRUVYLHZ0dNRoND548CA8PLyvr29/f39oaIhEImVkZCCRSI1GMz093dvbGx8ff//+/fb29qGhITQaXVJS4nQ6t7a2hoaG1Gp1c3NzWlra7du3qVQqZGWWl5cJBMLly5e//PLLrKwstVo9Ozvr9/sFAgESiWxsbAS+sZ9of58rDZFIPLvSzMzMQM63sbGxo6ODTqdXV1eTSCSgYhOJREgkMjIy8saNG5GRkYWFhVQqVafTvbGnOTw8hP0yhUJ58ODB5cuXQX6NSCSiUCiFQgGtkK2trfHx8enp6VqtNhgMWq1WHo9XVVWVlZVVUFBAJpN1Ot3s7Kzdbs/Ozr506VJKSgqJRCISiUKh0G6319fXP3z4MD8//2wa5PDw0GKxQIhdVlYGEWJ4ePjvfve7iIiI6OjoS5cuxcTEUCiUioqK69evX7lyJSUlpbq6urq6OiUl5fvvv//mm28eP35cU1OjUChMJpNSqcRisTdu3Pj8888xGIzH4yGTyb///e8TExOVSiWPxyssLCSTyRqNxmazTUxMQKE+KSmpoKCgu7ubwWDcvHkTgUCcHYIHBwdms7m6uhoUHyIiInA4nFarlclklZWVXC53aGiooaEhOjqayWQGg0GNRoNEIqFenZycHBYWJhQK/X5/e3s7Ho9nsVgOh2Nubk4gEISHh2dnZ0NMgMfju7u7zzZuwZ5GLpfX1dVFR0d/9tlnFRUVo6OjXC730qVLCATC5XK1tLRkZmaSyWQul5uQkPDNN9/ExsZCXF9dXa1Wq6lU6oMHD8rKyvr6+uh0elRUFJ1O7+/vr6ioiIuLU6lUPp+vtLQ0Ojq6tbV1fn5+fn5eIBBEREQ8evSIQCBwudz6+nqFQqFQKEpKSr788stf/vKXT548UavVZ+tAo6OjAoGAw+EoFAqpVArlFoFAMD4+PjAwkJycfOnSpaamprOjzmazoVAoOp0e6jsaGRmRSqV1dXVyuXxsbAw+HB8fLyoqysjICMmrgykUivT0dDQarVQqUShUVFQUm82GNE5+fj7k4hkMBmyylUpld3c3jUYrLCyEd9HQ0JCeni6TyYaGhrKysr766isymQzPE4PBiESi6enpvb299vb22NjY8vLyvr4+Npv98OHDpKQkoVBos9l0Oh2dTn/27FlcXFxSUlJWVlZVVRWXyz3Lub6+vm61WhkMRmJiIrwajUbjcrmQSGRmZqZer3e73VQqlUgk9vf3Qw5QpVIZjUY0Gv3kyRMWizU/P7+2ttbb20smk1EoFI1Gq66ujo6OTkhIYDAYMF9YLBYOhyMSibBX0Ov1bDYbiUSSyWQej8dgMKRSqd/vd7lceDz+wYMHDx48wOPxoeaCNwxaXTo7OysrK9ls9uTk5MDAABqNBqETq9VKJpPLy8uxWCwejxeLxcFgMBgMcjgcDAYDRREej4fBYDo7Ozc3N1+8eKFWq2NiYm7dulVQUECn01UqVSi28Pv91dXVOBwuEAgYDIbw8PDY2NjBwUEYUWw2Ozc3Nzc3l0qlSqVSKpV6+/btBw8edHV1DQ0NVVVVlZSUuN1uaJpoa2vj8XgxMTFfffVVdXU1pGo3NjZoNNqVK1c+++yz7Oxsm812fHy8srIik8ngZf3Ynrd32t/hSrO2tobH45OTk0MrjdfrLSsrKyoqMhqNU1NTKpUKj8ejUCgej6fRaFpaWsrKylJSUjIzM0GFGpJRb6Q+Zmdn9Xq9wWDQarWFhYWXLl16/PhxWVlZUlJSdnZ2KOlhs9kyMzPLy8vn5uZOT08XFxelUmlpaWlYWFhERERNTQ10o25vbxcXF3/xxRfPnj1raWmRSqVut/v4+Fir1T548CA1NTUUrp6enj5//txsNpPJ5NLSUpFItLi4aLFYbt68+ctf/rKgoKClpYVCoVAoFAig0Gh0Tk5OWlpaWlpaamrqkydP4uPjIVHb3d2tUqmampoaGhoaGhoSEhI+/fRTJBI5NjZWX19/9epVEom0uLjY0dEBC5XL5QqlaPV6fWpqKhaLnZmZ6erqun//fk5Oztk+tOfPn7vdbqFQSCQS8/PzwfWoVKqOjg4MBgMOurOzMzk5mUQiDQ0NCYXCwsJCyAHevn37iy++YLPZgUCgs7MTjUYTiUSr1bq3t+fz+dBoNETfDAbDaDS+Me4XFhZaW1tpNBqLxYqPj//Vr3717NmzgYEBHo8H27jh4WGJRAIpjpaWlsePH//3f//3o0ePqqqqcDgc7FcaGhqioqKIRGIgEGhsbIyKiuJwOGNjYxwOJyMjQyKRGAwG6GDs7e3d3NxcWVnp6OjIycnJzMyExGl9fb1IJBKLxbW1tY8ePfr888/Dw8OlUunZDpTx8XGhUMhms2UymVQqpdPppaWlBALB5XJ5PJ6CgoK7d++KxeKzd2c2m4uLi4lEYuiuBwYGmExmSUkJg8EAd3N6ejo2NgZ5MLvdHvrtq1ev5HJ5QkJCSUmJRCKB4rBAIJienoYVsaqqisfjiUQiKAILhcK+vr6Wlpby8nJYDIRCYU1NjdFo9Hq96enply5dam5uhq6N2tpaJpNpt9uhJSEpKam2ttbv96vV6sTExGvXrhUUFBiNxunp6c7OzoyMjDt37jx48CArK6uurq63t3d2dhZ6DV69erWwsKDVaolEYmxs7G9/+9ubN2/K5XK73Y5AIJ48edLe3u5yuYB1l81mM5lM2PeIRKKSkpJHjx5VVlZC3riuru7Zs2epqakwu+/du3f79m00Gq3RaAwGQ3NzMwqFqqio4PF4NpvNarWSSCRYhuvq6iorK2tra1UqVW9vL4lEevDgwbfffltYWOhwON7ZyANNa11dXfAYu7u7YemSSqWwkD958uTWrVuJiYk5OTlUKtVut7tcLhKJBIHd4uKiUCgsKSkhkUhQGRWJRBEREffv3y8tLa2pqcHj8RKJxOPxLC0tOZ3O4uJiBAJhMBgUCsWjR4/u37/f2NhoNpu7urrEYjGXy0WhUFlZWTk5OYmJiV988cXNmzfFYrHRaCwtLc3IyGhra3O5XHK5HJbb1NTUyMjI0tLSzs5OKGxzudzMzEwQR1YoFNC139bWVl5eXldXB67sJ9rf4UqzsrJSU1MTGxsrkUjgE4/HAzt3lUo1Ojra3d1NJpOrqqrodLpQKKTRaBUVFRQKpa2tDYL9a9euRURE9PT0nD2sWq3OzMzE4XB9fX00Gu3u3bsJCQllZWX379+/d++eVCqFr7lcrtzc3JKSEoiGJicnm5ubCwsLY2NjU1NTMRhMb2/v/v7+wsJCTU3NnTt3EAgEn89vaWlxOBz7+/s6ne7x48eZmZlvrzRUKrWqqkoul6+vr7tcrsjIyG+++YbL5UIDTF9fX09Pz8DAAEzLiIiIyMjI3Nzc7OxsaMFaWFjY2NhQqVSJiYmJiYlcLre6uvrq1asVFRVer7euru7777/HYrHQf1lYWAiBbShqBg+CQqHGx8fVavXjx48LCgqmpqbOXqTX6+3v7/f5fBqNpqCgIC8vr6OjA8Yrh8MZGRnp7OxMT0+Hu6iuroaQUyQSxcTE/PGPf8zPz+dwOGg0+tmzZ2VlZd3d3dAHBbPrq6++qqiomJube2PmDw8PV1RUpKenk8nk9PT0X/3qV7GxsSaTSSgURkdHo1Aos9nM5/OhkEChUJKTkx88eJCbm0un0wUCgdPpXFhYEIlEjx49gqicTCbfvXsXh8M5nU4+nw81Wz6fn5WVlZyc3NDQYDQaoUrB5XKbmpoEAgGFQiktLYUlQSgU1tfXp6WlpaSkyOXys/W2+fl5pVJJIpHweLxQKISiSFpaGpvN1mg0UGbQ6/Vn785kMkEmB+o0p6enFosFjUYnJCQgkUiz2QxZRJfLhcFgamtrvV5v6LfHx8dCoTA8PDw9PZ3NZmdnZ9+9e5dGo9nt9sbGxoyMjMLCQnCOXC4XjUaz2WxwOsnJybm5uVBKbGpq8ng8LpcrJSUF9AYXFxcDgUBTU1N1dTWHw+nr64NUFZPJnJubm5iYoNFojx49Sk1NhTcYCATIZHJcXNzjx48hjxcIBABOePpnwEpdXR0ej6+pqYmPj8/IyNDpdA6HIycnBy5YrVaTyeTs7OyMjAw4DgKBYDKZFAqlqKgoLy8Papzp6el37959+vRpc3Mzn8+PiYm5e/cuBoPRarU9PT319fV5eXmpqak4HM5gMNhsNgKBkJKSgsfjGxoacnJyEhISwL9zudySkpK0tDQymezxeN7J2Pv69ev19fX29vanT58+fvy4trZWKBQ2Nzf39fUFAgFINV+9ejUxMTE3Nxey8Uqlsry8HIlEQotgT08PEonMzc3l8XiQ+YiNjc3JyWloaIDnkJ6eDgUtnU6HQCCysrLa2tpEItHDhw+//PLL5ORk2L3p9frh4WG5XA53l5SUdO3atUePHvF4PLVajcViYbvT2toKGWY0Gk0gEFgsFh6PLykpgb7wjo4OyK9mZmbW19cD5qa7uxsSwj8K2HCe/R2uNJOTk3l5eVevXsVisQC28ng8eXl5jx49AjkDjUZDpVIhQ11RUZGXlwfNUU1NTWw2OyMj409/+lN0dLTRaDx7WLFY/N133929e7e2thbCw4qKCjab/fTp00uXLqWmpsrlcovFotFoSktLs7OzGxsb+/r6VCoVDodLS0srLS3lcDg0Gg1iqObmZiKRCPV/CDQ6OzuXl5eNRuOzZ8+Ki4uHh4dD6KqjoyOXy0Wn03Nzc2k02vj4+NTUFJFITE5OplKp0HCl1+s1Go1er1er1dXV1XFxcRUVFZDcKysrY7FYQ0ND6+vrPT09T548uXv3LrQDJCcn4/H4vr6+urq6uLi42tpat9s9PDwslUqxWGxlZSX0gPl8vtbW1uzsbBwO5/V6oQGmpqbG5XJtb2+Dyzg8PITdvdFolMlkaDQanJper8dgMEwm0+VygR/HYrEMBqOmpqayspLP5ysUCgaDkZubG8qkl5SU4PF4WJJPT0+np6dLSkq+++47HA73NsJmfHwcUqM0Gq2ysjIiIgKJRFqtVo1Gg0ajWSyWwWBQKpU0Gg2Px1OpVAaDwWAw6HQ6i8USiUTQktvX1wflEL1ez+PxEAgEh8NxOBxarZbP57e1tTU1NWVkZERFRUG839LSolar3W53IBCw2WyNjY1VVVXV1dVcLlepVMrlcnitNpvtbJPo7u6ux+Ph8/l4PL69vd3n87W1tZWVldXU1LS0tIhEIpVK9UYTucPhQKFQRCIRsvavXr0aGhpisVjFxcUMBsPr9R4cHADegkKhSKXS0IIEbwRGIwaDEYvFUJBvbm42m81isRjKRZ2dnTabzWg0ikSi9vZ2k8lUX18fFxcHa2pvb6/L5Zqfnx8eHmaxWEgksqOjY2lpaWNjw+FwNDU1cTgcqGBDz9ju7u7BwYHL5eJyuVwu1+PxnJyc7O7ums3murq62tpaLpdrsVhWV1fPAnuhI6ClpaWtrU0gEMjl8vHx8YmJiYaGBiQSKZFIbDabRqNpaGjA4XBIJBKDwUA2wmQyqdVqSElBZgyNRvN4PLfb7Xa7uVwuFottbm6GujfgOlksFmiRTExMqFSqxsbG7u5ug8FApVJhNPb09Gg0GolEIhKJDAbDeYDrV69era+vq9VqqGVyOBy9Xg89fjCLSSQSFovl8XhisVipVDocDugRkEql0DE4OTnZ2dnZ0NCgUChgTvF4vM7OzsHBQaVSSSAQ8Hh8W1ubz+cbHByErjy73d7a2gqp+7KyMg6H09bWNjU1dXR0ND4+3trayuPxGhsbKRRKfX09dBN0d3dLJJL29nbY9nV3d3d0dPT39/v9/p6eHijHQnvU7OwsDAO1Wj0yMrK6uhoIBNRqtclk2tzc/FBn/P/Z3+FKEwgEoPJcWlrq8/lOTk7GxsYwGExcXBwajVar1Wazubm5GYFApKam5uXlZWdnp6Wl5ebmFhYWZmVlPX36NDMzs6Gh4WzAfnp6ajAYUlJSbty4ER0dER2ODAAAIABJREFUDcmc1tZWi8XS0NAQGxt78+bN1NRUJpMJBQPozoLCQE1NTV5enlAoBM+Snp7+6NGjgoKCpqYmaJltbGyE/NLCwoLP5wNv6Pf7Q8HUy5cvJyYmoFpbXV09MDCwt7cHHqe8vLysrAxqTh0dHdDrWVBQQKFQLBbL+Pi4QqGAtE99ff3Q0NDg4CCdTi8qKgJ0JIvFkkqlBoMBuoZaWlo8Hs/29vbCwoJKpUKj0QgEgkAgtLe3t7e319XVSaXSQCAAnaBisbi/vz8EPn/58uXs7GxXVxcej6+srORwOIODg9vb2xMTE3K5XCaTeTyeqakpq9UqkUh4PF5bWxuk3R0Oh9/vNxgMZDK5rKysrq6uvb0dcBVQj1leXoaivUqlervhEhAtMplMJpOJRKLm5ube3t6xsTGfzwewCbfbPTo66nQ6Ozs7Ozs7YXlQq9WNjY1yudzr9QJEw2KxWCwWv9/vdDr1er3D4ZicnJyamoL/qtXq7OzssLCwwsLC5ubmnp6e0dFRwDZubW3Z7faOjg44F3SyQT12fX39LMDw1atXOzs7LpdLoVC4XC4Ayul0OnCyAwMD6+vrb0BwAO3B5/NtNtvGxsbx8fHCwoLFYlGpVPDJ6upqe3s7Fottamryer1nW6QAaGI0Gvv7+6F4YDAYPB4PlIWgV3hycnJzcxNwgiMjIw6Hg06nJycnl5WV6fV6wNwACcLMzMzk5OTc3BzghLa3t8fGxmw2m81m8/v9S0tL+/v7QPYDeMm1tTVYZYFjAhqdh4aGZmdnz66+0LoN8J2BgYFAIABY/f39/ampKZ/PNzMzs7W1tb29PT8/HwgEoMF6bW0NIKLb29vT09Ner3dkZGR2dhZ0RoAlbHl5eWRkxO12Q+840Cmtrq5ubm5CR9n29jbgOtfW1jwez8DAQDAYXF5eHh0d9Xg8k5OT8DreiRh78eLF/Py8VquFfmifzwerLFBb7e7uArhyfX19Y2Nja2sLWp8BMQqcWAD5hOsBGNP6+jogW4FwaHFxcWNj4+DgAPAYGxsbe3t7HR0dt27dCg8P1+l0y8vLgD89PT09Pj7e3NxcW1uDewQ4LVBzbW5uwive3d3d3t7e2toCoRa4yMXFRXhiAFnd3NwEAosXL14AsudjcfD8va00r1+/XlhY6OzsZDKZbW1t09PTJycna2trBoOhpaVFqVR6PJ7Z2dmhoaH29vbm5maJRNLa2ioSiaDfnMPh8Pl8AG2dzbC/fv16dna2s7OTTqdTKBQ2m61UKgHCEggEoDueQqGAB3G5XN3d3SKRSC6Xwyajo6NjZGTk+fPno6OjjY2NWCy2sbFxYGAA0C0Oh0Oj0TidThgrTqcT0t9n1RO2trY8Hk9bW5tCoZiamoL57PF4ZDJZQ0NDa2trf3//4OAgABokEgmsRi9evIDQCcKlsbGx5eVlr9cLK5zVavV4PCMjI6OjowDo8Xq98/Pz4ByDwaBWq21paZHJZGaz2ev1Dg0NgQLQ2toaYN3HxsbW1tZCaPPt7e2hoSF4nqE21r29vfHxcZAs2t/f39raAo82OTkJVEBLS0tACwTPYXBwMBgMAjvI2tqaz+fT6XRtbW0Gg+FtFg0AVG5ubs7MzAQCAXA3gCsCKPXCwsLKygpMOcBC7e/vv3jxYnp62uFwuN1u6EmFiQfzGSYbeDcg0Xnx4oXFYklNTb19+zYGg4HE+lmfvr6+PjMzA24L/C+sQ+8copubm9PT06urq/Dc1tbW/H6/z+d7J0vF9vZ2IBDo7u7u7Oz0eDz7+/uHh4fr6+tLS0tbW1svX74MBoNNTU0EAqG3txeQ4aHfAv4UnMv2n213dxe8D5DLnV25V1ZWent7y8vL4+LiCARCKH8LJF1v/w1IJkAv/eDEBNoecMdvc7qcnJxsb2+vra29zT/0Pj7uApKYnZ2d97m8w8PD0H2BR74YZ31wcODz+Xg8XmlpKZvNPruV/Pns1atXTU1Nv//9769fv24ymf4CZwzZP1aaNy3EewFRDIQkL1++PDg4gPX58PAQwN57e3vb29s7Ozsw92BCwuIPS/obBJEAkwYXBmEI8HLC6dbX10MhyeHhIURbEHYBMjEUemxtba2trW1tbR0eHgK73/PnzwHDDBweR0dHEGKcpb6Az3d3d+Gm4HNw0KFrPjw8PMslCt8JPQ34EMg8gBjj+fPngLcHUo0Q1Sv8EGIccE/gi+E7oDwEx4EDns2EQKgY4iAJPTr4IXBcwgXAEw7JEQEtCpwIngPkhcRiMQ6Ha2lpmZycfHvyAy1NiCn1+PgYyCtPzhhcIVxG6LVC/ygMhjdIV0OXfdZ/DQ4OZmRkRERENDQ0LCwsvDE8QhTC4IjhwV5MZhM6ODyQs9yvb3z54ODA4/EoFAqLxQLUJmeZQyGyBpjwG2c8O35C/D1nf/7G95eXl7u6uqCLncfjnYeieOPGfxQ17QX0pm888I9lF5zxp/xkf38f0gMZGRl4PD5UzvxZbW9vr7Gx8bvvvoPWsp/CCviXt7/DleZv6LD/sAsMMoQ8Hg+ggu8ka/mLvZfx8XHoqRMIBDMzM39hYqH19XW/3z8xMfGGc3n9+vXOzs7MzEyIseKnGOQhORwOi8Xq6+v7WDQkf38GaNlgMGg0GltbW3U63dLS0l9gKB4cHADnFp/P93q9f1sv6O9tpfmH/d3Yzs4OkDh0d3cPDw//dXnvV1ZWjEajWCxWKBR+v/8jMg++j8G+5w1aSTDYF36U3cDBwUEwGPR4PMAY9LdL0/dzW2gbDYIgh4eHfxnFFxgGUDmDwRDKCvxMFxDa/v70Q/1jpfmH/R81EGWZm5tbWFjY2dn5y2xfzsucHB4eAjPbxMTE0tLS31bi4j0N+Ib39/d/rOjWP+yvZa9evQLCrfn5+efPn3+UOXKWzxs6Gt6m9P4A+0krzdm89of9PBQdgBLRe8pDAXn4Tzk1pOlDkwpCA/jk4ODgrz7NoEYSIlGHQAb+d2dn5z1f/NmwC8rdQDAMITBERu8jUwEXA5TGP/nOfpx9QJL9o5zx5cuX6+vrCwsL7+w++ikD/vj4eHd3F+p8P6saVUhTDlqtPuCaoZ50cHAA/REfy5G9bUDwury8DLptk5OTo6OjwA+7v78fDAZnZmYuzg1COgsG+fb29jsRMH8TFtqjvH+7F9BqgHrNj1oSgJj8vEn94sWLYDDocDi8Xu+PVWB7p/3olSZ0/0COvbu7+2FpDejz297eXl1dnZ+fDwaDS0tLOzs7PyjpeHR0BJ18IIPxAac+PT3d2Njw+/02m83r9a6vr7948WJra2t4eNhmswFV8Icd9mPZ9va22+2WSqXNzc3QhwYUIAKBwGQynWUbO8+A/nlxcXFqagpkC+RyOaAQFhcXt7e3R0ZG/H7/5ubmDw5oYEwaHBz8WBI+f0WDPMMPfm17e7utrQ0IQBcWFt5/SYBRDf0Ob//rwcHBzMwMcB77fL6PvjGCNRK81fLystVq7ejo0Gg0IPHy/seByO/g4GB9fX10dNRgMBgMhunp6Z8pP+NwOADIAuzL2dnZ0dHROBzO5/PNzs6C4tTk5OTFF7y4uGi324Fj+30myP9Ng60zEKKfJ1l0+v+PdfR6PRCGejye90/qnpycjI+P2+32mZmZt//15cuXCwsLer2+paWlp6fno0z8D1xpXr9+Dd2rgUDgw5g+j4+Pl5aWgI21s7NTq9WazWa32/2Do2R/f398fHx0dDTUX/sBNjY2JpFIqFSqRCKZmJg4ODiYmppqa2urr6/v7Ox8n55FiKHe0J76WAYkTkClLJVKR0ZGBAJBXFxcZmYmEBX/4BFevXo1Njam0+m0Wq1arQ7BnisrKzs7Ox0OB3AKOJ3O+fn5i93Q6upqb28vlD0/3i3+JSw0PI6Pj0FUZnl5+X38+8LCAhKJvHr1alFR0Vnmqx90tUdHR4FAAHgHQh+G6ihzc3NKpRIQGE6n86dXdKGhLnRV+/v7o6OjoD4CGpRcLre5uRnoJ852rJ1dcaElL3RMkGCYnJwERIjb7QY0Vai9Cpow336MkHz7UWE1iHfJZDIMBiMUCg0GA4PBuHXr1r/9279Be5Xf7+dwOCgUqru7GyLCdx4H2ta7u7u5XK5MJgu14cF2HC4VlNlAEwhUjuAhAHZnf3//bPc2/Cv8AR8ChAgyCnCEUAoEJGXhb3jRL168gIby9wlrDg4OVlZW1tfX9/b2FhYW7HY70OeMjY1BLyt0hEJi46x27fPnz4PBII1Gi46OLioqMpvNsDhBiAD5D/g5NM2GpJ2h31WpVKLRaIlEApMC0DPQyLq4uOh0OmUyWXNzs8lkeh9lqR+0D8yewd6qu7u7q6vrDVTzWbtgZkJnUUNDQ0lJSXl5OdBGSaVSj8dz8fqxvb09ODjodDqXl5d/cOaf7e88a4ODg0D2TqFQvF7vzs7O4OAgyAG0tbX9oCuHBlyLxeJ0On8O/7uzs2O322tqarKysgAHQyQSr127lpOTY7Va32czCxRqBAKBx+N1dXU1NDSUlpbm5eUBOVJdXZ3VatXr9Vwu9zyNstBD29zcBITzRyEPf/ss7x8ugI97z6UdXANkWYPBoF6vVygUgHb8wd+OjY2VlpZev369tLQ0RH8HumFv7OChiTy0Zmxvb7e0tNTU1PT19cEnoOsKwtIul4tAIAA/ytLS0hs38nZXPTS7h27njZ7s09PTvb09QOzD/87OzoIOxdDQEGC8+/v7QXNleXkZMmnQ07+6ugoaSC9fvlxdXT0bQQM+rLOzMxAIrKyszMzMOJ1Op9MJIeDR0dHc3JzX652cnAQvDM4atNUDgcD09PQFwfgb9zs1NdXd3Q3cdzqdzmw2G41GFosVExOTkJAAfMY9PT1MJpPJZIYkv07fciwvX75cXl4eGhrS6/VmsxmgWs+fP19cXPR4PBMTE7u7uysrKwDwBLgVrKMLCwuw6fd6vcFgEBaYpaWl6enphYWFxcXFxcVFcO6Ae3M6nbOzs+CRR0dHh4aGJiYmgsHg+Pi43++fnJwElp2lpSW73Q4Bx9spn7MXf3Bw4PV6gX8MYhRgD2GxWCqVyu12w2FBOsvv94+MjMD0Pz4+HhkZEYvFMTEx33zzTWZmptlshqBheHhYqVQC+wNoULlcLo1GAxED7Pk2NzdZLNatW7eysrL0ev3ExEQgEABsL6BxoRPH4XDMz8//1fRpQHx0YGBAIBA0NTUNDQ3t7OwAmm9sbGxsbCwYDL4BInvbNjY2dDodGo3Oysqqqalpa2tTq9VtbW0gPgpgXcDWgiA8aAWura2Nj48DER5wLe/t7a2srCwsLABb6sLCAowekDg9b6XxeDx0Oj0vL49AILjd7q2tLb1eX1tbC7JLIP00Pj4+PT29srKyuroKSqszMzOgKtbT08Pj8ZBIJPCfr6ysLC4ujoyMuFwuv9+/srKytbU1OzvrdrsHBwdnZ2ehUgKSf263G7DQICX7zoezt7fndrvZbDYIlgSDQSQS+cc//hGFQr1PZg9opzkcTmFhYVNTE/C3y2Qy4BK9detWUVGR1+u1Wq3A8PjOPRw8tJBCe09PD4AiR0ZGhoaGfD4fCAiCKprX6x0dHQXoIuC9PR4PoEFBMw1QRBMTEy6Xy2azeTwekH2EL4O+GSiDhWTcNjc3l5aWZmdnIbO6vLw8NTU1ODhoMpkcDsfMzMx55QeIDQFPPjc3NzMz09vbS6FQQHOlr68PFOpGR0dD8msgywjucnJyUqfT5ebmPnjwAIvF+v1+wCeOjY1ZLBatVmuz2UDiHlZrs9lsNpvBuQeDwYqKilu3blGp1GAwOD09PTg4ODg4ODY2NjExodVqmUymRCJ5J2VhKFuwuLhoNBo7Ozth2ptMpv7+fqvVCkQpAEff2dmZm5vzeDx9fX1qtdrlci0tLZnN5oyMjCdPnjQ1NcFzttls8EdfX5/RaLTb7SMjIyMjI1ar1Ww2g56ex+PRarWAVt7f33c4HFgsFo1Gw97XbrebzeaBgYG5ubnV1dXh4WG1Wi0Wi7u6utxu99jY2ODgoMViAS1RwPnabLalpaUfDOdfv37d399PIBAaGxsDgQBwEEASrLKyMj09XSQSAXpXpVKVlJQQCIRQDu2N9w4c/jCzPB7P4OAgyOK1t7eDnptGowGtaKBvBwEbjUYD8Oq2tjaQ/BgZGZmentbr9WKxWCqVqlQqIG4ZGxtzOp1KpbKlpUWhUPh8PpDNbmhosFqtIyMjoBY6NDQ0Ojrqdrv7+/uB6kYgEAwMDLyxzwtd/PLysl6vb2hoACR4SB8oPz8fuF97e3tBwHd0dDQQCIjFYplMBlhjEN9kMplRUVGXL1/Oz883mUwLCwt+v7+zs5NIJFZUVIBkZ0dHBxaLLS0tJZPJOBwOg8GAWiCBQPj0009BVgNElYA1Q6vVGo1Gm802Njb2USo0YB+y0oSyePX19SDq4Ha7FQoFk8kkkUgkEonD4VgslouhucvLyx0dHTgcjkajabVa0KkdHR1VKpUcDqe+vl6pVLpcruHhYbfbrdFogM1Qr9cDA4RIJAKFVzi1WCxuamri8XgtLS3Nzc0MBoPP5/v9/vPOHgwGFQoFDoejUCh2ux1oBUDya25ubmBggM/nE4lEUAFRKBQNDQ3Ar04gEMrKyoCPD1QGgBkMmFmB9k6lUplMJh6Pl52dnZKSwuFwgMGlqakJUljJycm1tbVWq/W86G9paQkeL5/Pn5qampuby8vL+/TTT2tra38wO/H69WvgOKmtra2pqdHpdODlg8Ggy+WiUChAYwxQ9vz8/IqKivOo0U9PT4+OjkAah0AgmM1mwJCnp6cjkcjCwsLk5OSCggJgv66qqgJ6QTabnZKSAoJpIKUjkUjgtxQKJTExMSoqqri4uLGxESjCQA6koqICGPUzMzPz8/Pb2tpMJpNUKuXz+a2trXK5XCqVymSyurq6zMzMlJQULpc7Ozv7zqV6fHwcmMra2to0Gg3MorKyMqDzwuFwdXV1NTU1EFUA+X9JScn4+Pj8/LxcLufz+SwWKyoq6sqVKzU1NXa7va+vTyqVtrW1USiUEPUhg8F4+vRpWloakUisrq6uqKjQarU+n6+oqOjLL7/MycmRyWTAYygWi+EyFAqF3W6H2Pm8B35yctLb2xsXF/fdd9/l5+dXVVUlJCSkpaVBTBYVFcVgMAKBgN1uB40vPp9fVlZWUVEhk8kEAsHjx4+///57kGLEYrFUKhWYH+l0OsgOQUgnFAp5PB5ISKjVagwGEx8fTyaTYWlEIpEASIQBTyQSuVyuWq3WarUCgYBMJgNrHJlMhjFWVlYGbHUoFKqkpASNRuv1+h8MhF+/ft3V1ZWXl8dkMldWViAZNTs7K5VKo6Oj79+/z+VyIR/V19eXlpaWn59/3ow+ODhwOp2gZalWq5VKJZ1Oz87OzsvLA2kGGJAUCgW4mpqbm3U6HSgLVFZWNjQ0oFCokIYFjUYDFr6amhqhUAgqU11dXQaDATjWYEAiEIjCwkKDwQCKQcBRplKpkEgkcJViMJjIyEgGg3GeJ7RarQgEIicnp7W11ePx9Pf3s9ns/Pz8goICLpfrcrmsViuBQECj0TabbWBgoLq6GsjgR0ZGmpqagBWJRCLBXeh0OpVKVVdXV1dXRyQSc3JyCgsLeTwe6IM8fvy4sbERdAUbGxunpqbIZPJXX32Vk5Oj0WhA2QGUqEwmk8vlCgaDPx2hddY+cKUJBoPAvQ9BYk9PT1FRUVRUVGFhYUlJCVy02+2+oOkFCHSrq6uZTKZarQb6qb29PaD7TUlJYTAYSqVSpVK1tLRUVFTExMTk5OQAWxzIC4JDb2pqQqFQxX82oMvMzMykUqkej+e8W9jb2wsEAiBYCQyswJMKfEdAawozB4lElpSU5OTkPH36ND4+HvxgYmLi3bt379+/X1RUJJVKOzo6cnNzv/nmG+BmplAodDq9vLwclFoyMjLEYrFWq6XRaCAqc/ny5aqqKqvVel6mfmRkpKWlhclkKpXK5eVl4Az9+uuv6XT6D76dk5MTr9fL4/HQaDSXyw1NzqOjI5CwBIHFlZUVh8NRXl6OQqFcLtd5vu/o6KinpyclJSUnJ0en04nF4ps3b165ciU3NzcsLOw//uM/bt++XVJS8vjx47CwsNbWVpfLVVhY+MUXX0RERJSVlZWXlyMQCKCDFAgECATi0qVL165dy87OBulJOp0OMmipqam5ubkgHhMREcFkMrlcbnFxcVVVVWNjIw6HA73UgoKCb7/99rPPPissLHS73e90Z16vl0ajZWZm5ubmotFo4NOsrKwEaSwMBlNeXh4ZGVlcXAyMn5988smVK1dMJhPoStFotObm5szMzDt37hAIBI1GA464uLg4MzPzyy+/vH79OhaLLSoq+t///d/79+8DojM8PJzH43m9XgwGA6rSQqEQgUDcv38/JSUFpEq6urreiT994/XJZLL/+q//+qd/+qfU1NSioqKvvvrq+vXrKBQqOTn5q6++KikpARmY5ORkIpGoUChIJFJ2djYSiUQgELdv346MjIRFpaioCIFAEIlEkHktLS3NzMwExyoSiWQymUajAcKh+Pj4//zP/0xISPB4PH6/H4PBFBQUUKlU2AiCdlxxcTHIkYHbBbq/77//Pi4u7unTp3FxceXl5UwmMz8/Py4ujs/nv89KI5fLQZ8pxOG4vLzc3t6emZkZFxdHJpMBrNrf3w9Rgtvtfueh9vf3jUYjlUqtra3lcDgSiQSHw0VGRmZkZLS0tNTW1l6/fj0pKYnP5yORSBhdfX19CATi22+/raqq0mq1jY2NFRUVoDKJRCLT09NB3qKjo6O2tjY5ObmpqWl8fFyj0aBQKBwOh8fj09LSEAgE7HuAEcrj8bBYrCtXrqSlpSkUCiwW+/DhQzKZfB5Dpdlszs3NTU1N5XK5Wq1WKBRWVVXl5eXV1taCOEUgEAC+Z5vN5vP5iouLs7KyoGgK6rErKysmk6mkpIRGo2k0GgKBkJCQUF5ezmKxUCgUFosFrtvPPvvs0aNHBoNBLpfHxMQAYSudTv/+++9JJBIQViEQCGDJYrPZwPZ78ev7sfaB2bOlpSWFQgGhqN1uNxgMjx8/vn37Np/PF4lEKSkpycnJEonkbaKqkAWDwfr6etC4rK6uZjAYIAzX2dkZGxv79OlTHo8HlJEQkoSFhRUUFHR1del0OiQSCQsPCoVCoVCwKlRUVJSVlSUnJ4O8VU9PzxtSZmft5ORkc3Ozra0tPz//2bNnFAoFqHn9fj8wPQOvO5fLzcrKiomJycrKSk9Pf/r0KWhEAgshkBkvLCz09fUlJiZev36dRCLBViknJ6eysrKysjI3NzcnJweLxYLYZV5e3s2bNwsLCy0Wy/r6+nkPx+FwkEgkKpVqMpmWlpYGBwdLS0tjYmLeEC95p718+XJgYIDNZoOiX4gndGJigsFgVFVVqVSqtbW14+PjgYEBUCOHDeg7e3lfvXpls9mAYd7hcCiVyrCwsNTU1I6OjpKSkl//+tcpKSkqlQp4ztvb2wOBAAaDefDgQXV1tdVq9fl8IpEoIyOjqKgIBBqysrLodHp3dzcWi01MTKyvr4f0NJ1OT0lJCQ8PT0pKqqmp4XA4wKhfV1dnt9vxePwXX3xx/fr1goKC6Ojo27dv19TUeDyed5b3JycnuVxuTEzM999/n5SUBNS2IMkM3MNAV1xaWjo4OCgQCH79619//fXXnZ2dvb29RCJRJpO53W5g/mcymSKR6PHjx7/5zW8ePnyYmZkZFRWFQCBaW1tBxQT8PjBhNzU1jY2NMZnMhIQEoVA4ODiIx+O/+eab3//+9yDB2dXVFUpHXEDKotFo/vCHP/zud7/jcrkSiSQiIiI1NRWkfBMSEmpra9VqdWFh4bVr18hkcjAY9Pv9XC63sLDw4cOH3377bUFBgclk8ng8AoEAjUZTqVStVmuxWKhUalRUVHR0NJlMtlgswWBwcnLSaDRyOJzw8PBf/OIXsbGxLpfL5/ORyWQ8Ht/V1QUuuLa2NiMj4+7duxEREWg02m63r6ysaDSaR48effHFF8nJyRUVFZWVlaC4TKPR4uLi6uvr36DRfOedSqXSpKQkAoEQ8sXHx8ezs7M6nY7JZNbU1IDL6+vri4yMfPLkSUiP540DPn/+3G63MxiMsrIykJrl8/kgaQhEfDExMZWVlXa7vaGhIT4+vqmpye/34/H4qKgoPp+/uLjo8/n4fD7Ip6LRaDQaTSKR+vr6RkdHiUTirVu3iEQiyCUwmUy4XwwGAxLRLBYLTup0OnE43O9+97urV68SiUTYEYJ0wtsz6/T0dGZmprm5GSKYnJwc2N8UFhaCDODR0dH09HRVVVV2drbFYoHtcnJyMmzdysrKILtotVpDEtrl5eW3bt1KSkqCs4OEXUNDw5UrVxITE10uV09PD+zCPR4PiUS6ceMGhULZ3NwE/dCqqqr4+Phbt26VlJRckBD6MPuQleb169cbGxtKpTI1NTU/P9/j8QwNDcXGxj558sThcAwODoIsK5fLfSdXFdj09DRwxYOkEofDcTqd29vbcFhQdwfRNyQSSSAQQCDZaDTq9XoGg5GQkHDnzp2UlBQWi9XZ2SkWi8lkclFRUXZ2NhaL1el0KysrF2eKj4+PJRJJeHj4119/XVBQYDabV1ZWrFYrk8mk0Whyuby/v18ulxcXF0dFRSUnJyMQCBqNNjQ0dHBw0NnZCYKbQDjW19eXlZWVnZ3d398Prvbhw4fJyclIJBKPx1MoFBaLBZoZNTU1kFu4OAkGe0Q